All-solid-state secondary battery

By adding fibrous carbon materials and adhesives to the negative electrode active material layer of all-solid secondary batteries, the problem of lithium batteries being prone to ignition and explosion in short circuits is solved, and higher safety and circulation characteristics are achieved.

CN119812431APending Publication Date: 2025-04-11SAMSUNG SDI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410686624.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-11
Filing Date
2024-05-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing lithium batteries are prone to ignition and explosion in short circuit situations, and are not safe enough.

Method used

Using an all-solid secondary battery, the circulation characteristics are improved and volume changes are suppressed by adding fibrous carbon material and adhesive to the negative electrode active material layer.

Benefits of technology

Reduces the volume change and internal resistance increase of the battery during charging and discharging, improving the safety and cycling characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812431A_ABST
    Figure CN119812431A_ABST
Patent Text Reader

Abstract

An all-solid-state secondary battery is provided. The all-solid-state secondary battery includes a positive electrode layer including a positive electrode current collector and a positive electrode active material layer on at least one side of the positive electrode current collector, a negative electrode layer including a negative electrode current collector and a first negative electrode active material layer on at least one side of the negative electrode current collector, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, the first negative electrode active material layer includes a negative electrode active material capable of forming an alloy or a compound with lithium, a fibrous carbon-based material, and a binder, and a ratio (B / A) of an initial charge capacity (B) of the first negative electrode active material layer to an initial charge capacity (A) of the positive electrode active material layer is about 0.01 to about 0.75.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0135167 filed in the Korean Intellectual Property Office on October 11, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0002] The embodiments of the present disclosure described herein relate to an all-solid-state secondary battery. Background Art

[0003] Recently, in response to the needs and / or expectations of the industry, the development of batteries having high energy density and safety has been actively conducted. For example, lithium batteries are used in various applications including information devices, communication devices, and vehicles (e.g., electric vehicles, automobiles, and / or cars), etc. In general, vehicles are related to the well-being of users or people, and therefore, the safety of lithium batteries is important or vital.

[0004] Lithium batteries using liquid electrolytes are relatively more likely to catch fire and / or explode in the event of a short circuit. All-solid-state secondary batteries using solid electrolytes instead of liquid electrolytes have been suggested or proposed. Solid electrolytes are less likely to ignite than liquid electrolytes.

[0005] Thus, by using a solid electrolyte instead of a liquid electrolyte, such an all-solid-state secondary battery can or may reduce the possibility of fire or explosion. Thus, the all-solid-state secondary battery can or may provide improved safety. Summary of the invention

[0006] Aspects according to one or more embodiments relate to an all-solid-state secondary battery having improved cycle characteristics and suppressed or reduced volume change during charge and discharge by including a fibrous carbon-based material and a binder in a negative electrode active material layer having an initial charge capacity less than that of a positive electrode active material layer.

[0007] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments of the disclosure.

[0008] According to one or more embodiments, an all-solid-state secondary battery includes:

[0009] a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer,

[0010] The positive electrode layer includes a positive electrode current collector and a positive electrode active material layer on at least one side (eg, one side or both sides (eg, opposite sides)) of the positive electrode current collector.

[0011] The negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer on at least one side (eg, one side or both sides (eg, opposite sides)) of the negative electrode current collector.

[0012] The first negative electrode active material layer includes a negative electrode active material capable of forming an alloy or a compound with lithium, a fibrous carbon material, and a binder.

[0013] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer is about 0.01 to about 0.75,

[0014] The initial charge capacity of the positive electrode active material layer is calculated by charging from the first open circuit voltage to the maximum charge voltage vs. Li / Li + to determine, and

[0015] The initial charge capacity of the first negative electrode active material layer is about 0.01 V vs. Li / Li by charging from the second open circuit voltage + to be sure.

[0016] According to one or more embodiments, an all-solid-state secondary battery includes:

[0017] a positive electrode layer, a negative electrode layer and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, wherein

[0018] The positive electrode layer includes a positive electrode current collector and a positive electrode active material layer on at least one side (eg, one side or both sides (eg, opposite sides)) of the positive electrode current collector.

[0019] The negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer on at least one side (eg, one side or both sides (eg, opposite sides)) of the negative electrode current collector, and

[0020] The first negative electrode active material layer includes a negative electrode active material capable of forming an alloy or a compound with lithium, a fibrous carbon-based material, and a binder. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings are included to provide a further understanding of the present disclosure, and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate example embodiments of the present disclosure and, together with the description, are used to explain the principles of the present disclosure. The above and other aspects, features and advantages of certain embodiments of the present disclosure will become more apparent from the following description in conjunction with the accompanying drawings, in which:

[0022] Figure 1 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0023] Figure 2 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0024] Figure 3 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0025] Figure 4 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0026] Figure 5 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0027] Figure 6 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0028] Figure 7 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0029] Figure 8 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0030] Fig. 9 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0031] Fig.10 is a cross-sectional view of an all-solid-state secondary battery according to an example embodiment;

[0032] Fig.11 is a cross-sectional view of an all-solid-state secondary battery according to example embodiments; and

[0033] Fig.12 is a cross-sectional view of an all-solid-state secondary battery according to example embodiments. DETAILED DESCRIPTION

[0034] Now will refer to embodiment in more detail, the example of embodiment is shown in the accompanying drawings, wherein the same reference numerals always refer to the same elements, and its repeated description may not be provided. In this regard, the embodiment presented may have different forms, and should not be interpreted as being limited to the description set forth herein. Therefore, the embodiment is described herein only by reference to the accompanying drawings to explain the aspects of this specification. As used herein, the term "and / or" includes any combination and all combinations of one or more of the relevant listed items. As used herein, when expressions such as "at least one (kind / person) in ... ", "one (kind / person) in ... " and "selected from ... " are placed before / after a column of elements, the entire column of elements is modified, without modifying the individual elements in the column. For example, "at least one (kind / person) in a, b and c", "selected from at least one (kind / person) in a, b and c" etc. can represent only a, only b, only c, both a and b (for example, at the same time), both a and c (for example, at the same time), both b and c (for example, at the same time), all of a, b and c or their variations.

[0035] Unless otherwise defined, all terms (including technical terms and scientific terms) used in this disclosure have the same meanings as those generally understood by those skilled in the art to which this disclosure belongs. In addition, terms (such as those defined in general dictionaries) should be interpreted as having meanings consistent with their meanings in the context of the relevant technology and this disclosure, and should not be interpreted in an idealized or overly formalized meaning.

[0036] Example embodiments are described herein with reference to cross-sectional views that are schematic illustrations of idealized embodiments. As such, for example, variations in the shapes of the illustrations that depend on manufacturing techniques and / or tolerances should be expected. Therefore, the embodiments described in this disclosure should not be interpreted as limited to specific shape regions as shown in this disclosure, but should include shape variations that are caused, for example, by manufacturing. For example, a region shown or described as flat may typically have rough and / or nonlinear features. In addition, corners shown as sharp may be rounded. Therefore, the regions shown in the drawings are schematic in nature, and the shapes are not intended to depict the exact shape of the regions, and are not intended to limit the scope of the claims.

[0037] The present disclosure can be implemented in many different forms and should not be construed as being limited to the implementation examples described in the present disclosure. Embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the present disclosure to those skilled in the art. The same reference numerals represent the same elements.

[0038] It will be understood that if (for example, when) an element is referred to as being "on" another element, it can be directly on top of the other element, or other elements may be present between them. Conversely, if (for example, when) an element is referred to as being "directly on" another element, there are no intervening elements between them.

[0039] In the present disclosure, terms such as "first", "second", "third", etc. may be used to describe one or more suitable elements, components, regions, layers and / or zones, and these elements, components, regions, layers and / or zones should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or zone from another element, component, region, layer or zone. Therefore, without departing from the teachings of the present disclosure, the first element, component, region, layer or zone described herein may be referred to as a second element, component, region, layer or zone.

[0040] The terms used in the present disclosure are not intended to describe only specific embodiments, and do not limit the present disclosure. The singular form used herein is intended to include plural forms (including "at least one (kind / person)"), unless the content (e.g., quantity) is otherwise clearly stated. In addition, when describing an embodiment of the present disclosure, the use of "may" refers to "one or more embodiments of the present disclosure". "At least one (kind / person)" should not be interpreted as being limited to the singular. The term "and / or" used herein includes any and all combinations of one or more of the listed items. The terms "including" and / or "comprising" used in the detailed description illustrate the presence of stated features, regions, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, regions, integers, steps, operations, elements and / or their groups.

[0041] Spatially relative terms such as "below," "beneath," "lower," "above," and "upper" are used to facilitate describing the relationship of one element or feature to another. It will be understood that the spatially relative terms are intended to encompass different orientations of the device in use or operation in addition to the orientation depicted in the figures. For example, if (e.g., when) the device in the figures is turned over, an element described as "below" or "beneath" another element or feature would be oriented "above" the other element or feature. Thus, the example term "below" can encompass both an above and a below orientation (e.g., can encompass both an above and a below orientation). The device may be oriented in different orientations (rotated 90 degrees or at other orientations), and the spatially relative terms used in the present disclosure may be interpreted accordingly.

[0042] "Group" refers to a Group of the Periodic Table of the Elements according to the International Union of Pure and Applied Chemistry ("IUPAC") Group I to XVIII classification system.

[0043] The "particle size" of particles in the present disclosure refers to the average diameter when the particles are spherical, or the average major axis length when the particles are non-spherical. The particle size can be measured using a particle size analyzer (PSA). The "particle size" is, for example, the average particle size. The "average particle size" is, for example, D50, which is the median particle size.

[0044] D50 is a particle diameter corresponding to about 50% of the cumulative volume when the particle size distribution measured by laser diffraction is calculated from the side of particles having smaller particle diameters.

[0045] D90 is a particle diameter corresponding to about 90% of the cumulative volume when the particle size distribution measured by laser diffraction is calculated from the side of particles having smaller particle diameters.

[0046] D10 is a particle diameter corresponding to about 10% of the cumulative volume when the particle size distribution measured by laser diffraction is calculated from the side of particles having smaller particle diameters.

[0047] As used herein, the term "metal" includes (eg, also includes) metals and metalloids (such as silicon and germanium) in either the elemental or ionic state.

[0048] As used herein, the term "alloy" refers to a mixture of two or more metals.

[0049] As used herein, the term "electrode active material" refers to an electrode material that is capable of undergoing lithiation and delithiation.

[0050] The term "positive electrode active material" as used herein refers to a positive electrode material that is capable of undergoing lithiation and delithiation.

[0051] The term "negative electrode active material" as used herein refers to a negative electrode material that is capable of undergoing lithiation and delithiation.

[0052] As used herein, the term "lithiation" and variations thereof refer to the process of adding lithium to an electrode active material.

[0053] As used herein, the term "delithiation" and variations thereof refer to the process of removing lithium from an electrode active material.

[0054] As used herein, the term "charging" and variations thereof refer to the process of providing electrochemical energy to a battery.

[0055] As used herein, the term "discharge" and variations thereof refer to the process of removing electrochemical energy from a battery.

[0056] The term "positive electrode" as used herein refers to an electrode where electrochemical reduction and lithiation occur during discharge.

[0057] The term "negative electrode" as used herein refers to an electrode where electrochemical oxidation and delithiation occur during discharge.

[0058] As used herein, the term "substantially" and similar terms are used as terms of approximation rather than terms of degree, and are intended to take into account the inherent deviations in measured or calculated values ​​that one of ordinary skill in the art will recognize. In addition, when used in conjunction with a numerical value or a range of values, the term "about" and similar terms include the stated value and values ​​within the acceptable deviation range of the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (e.g., limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, ±5% of the stated value.

[0059] In addition, any numerical range described herein is intended to include all subranges of the same numerical precision contained within the described range. For example, the range of "1.0 to 10.0" is intended to include all subranges between the described minimum value 1.0 and the described maximum value 10.0 (and including the described minimum value 1.0 and the described maximum value 10.0), that is, having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Any maximum numerical limit described herein is intended to include all lower numerical limits contained therein, and any minimum numerical limit described in this specification is intended to include all higher numerical limits contained therein. Therefore, the applicant reserves the right to amend this specification (including the claims) to explicitly describe any subranges contained within the range explicitly described herein.

[0060] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents not currently contemplated or foreseen may occur to the applicant or those skilled in the art. Therefore, the appended claims as filed and amended are intended to cover all such alternatives, modifications, variations, improvements, and substantial equivalents.

[0061] Hereinafter, an all-solid-state secondary battery according to example embodiments will be described in more detail.

[0062] All-solid-state secondary battery

[0063] The all-solid-state secondary battery according to the embodiment includes a positive electrode layer, a negative electrode layer and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, wherein the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the positive electrode current collector, the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the negative electrode current collector, the first negative electrode active material layer includes a negative electrode active material capable of forming an alloy or a compound with lithium, a fibrous carbon-based material and a binder, a ratio (B / A) of an initial charge capacity (B) of the first negative electrode active material layer to an initial charge capacity (A) of the positive electrode active material layer is about 0.01 to about 0.75, and the initial charge capacity of the positive electrode active material layer is charged from a first open circuit voltage to a maximum charge voltage vs. Li / Li + The initial charge capacity of the first negative electrode active material layer is determined by charging from the second open circuit voltage to about 0.01 V vs. Li / Li + to be sure.

[0064] The fibrous carbon material can provide a conductive path between multiple negative electrode active materials. Therefore, the increase in the internal resistance of the first negative electrode active material layer can be easily suppressed or reduced. The increase in the internal resistance of the all-solid-state secondary battery can be suppressed or reduced.

[0065] The fibrous carbon material can act as a support / buffer among multiple negative electrode active materials. Therefore, it is easier to slow down the volume change of the first negative electrode active material layer caused by the precipitation and / or dissolution of lithium during charging and discharging. Therefore, the volume change of the all-solid-state secondary battery during charging and discharging can be reduced.

[0066] The binder can bind the negative electrode active material to the fibrous carbon material. Therefore, the disconnection of the conductive path between the negative electrode active material and the fibrous carbon material due to the volume change of the negative electrode active material during the precipitation and / or dissolution of lithium during charging and discharging can be more effectively suppressed or reduced. The non-uniformity of the electrode reaction of the all-solid-state secondary battery can be suppressed or reduced.

[0067] The binder can improve the binding force between the first negative electrode active material layer and the solid electrolyte layer or between the first negative electrode active material layer and the negative electrode current collector. For example, the binder can improve the wettability between the first negative electrode active material layer and the solid electrolyte layer or between the first negative electrode active material layer and the negative electrode current collector. Therefore, the binder can more effectively reduce the increase in interfacial resistance caused by the formation of gaps between the first negative electrode active material layer and the solid electrolyte layer or between the first negative electrode active material layer and the negative electrode current collector. The cycle characteristics of the all-solid-state secondary battery can be improved.

[0068] If (for example, when) the first negative electrode active material layer does not include a binder, the first negative electrode active material layer is separated from the solid electrolyte layer and / or the negative electrode current collector, and thus, the surface of the solid electrolyte layer and / or the negative electrode current collector is exposed. For example, the exposed negative electrode current collector may cause a short circuit. The cycle characteristics of the all-solid-state secondary battery may be reduced.

[0069] Reference Figures 1 to 12 , the all-solid-state secondary battery 1 includes a positive electrode layer 10, a negative electrode layer 20, and a solid electrolyte layer 30 between the positive electrode layer 10 and the negative electrode layer 20. The positive electrode layer 10 may include a positive electrode collector 11 and a positive electrode active material layer 12 on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the positive electrode collector 11. The negative electrode layer 20 may include a negative electrode collector 21 and a first negative electrode active material layer 22 on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the negative electrode collector 21. The first negative electrode active material layer 22 may include a negative electrode active material capable of forming an alloy with lithium or a compound with lithium, a fibrous carbon-based material, and a binder. The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer may be about 0.01 to about 0.75. The initial charge capacity of the positive electrode active material layer may be charged from the first open circuit voltage to the maximum charge voltage vs.Li / Li +The initial charge capacity of the first negative electrode active material layer is determined by charging from the second open circuit voltage to about 0.01 V vs. Li / Li + to be sure.

[0070] Negative electrode layer

[0071] Negative electrode layer: negative electrode active material

[0072] Reference Figures 1 to 12 , the negative electrode layer 20 may include a first negative electrode active material layer 22. The first negative electrode active material layer 22 may include a negative electrode active material capable of forming an alloy or a compound with lithium.

[0073] The negative electrode active material may be, for example, a negative electrode material capable of forming an alloy with lithium or a negative electrode material capable of forming a compound with lithium.

[0074] The first negative electrode active material layer 22 may include a negative electrode active material, and the negative electrode active material may include, for example, particles. The size of the negative electrode active material in the form of particles may be, for example, about 2 μm or less, about 1 μm or less, about 500 nm or less, about 300 nm or less, or about 100 nm or less. The size of the negative electrode active material in the form of particles may be, for example, about 10 nm to about 2 μm, about 100 nm to about 2 μm, about 200 nm to about 2 μm, about 500 nm to about 2 μm, or about 500 nm to about 1.5 μm. In some embodiments, the size of the negative electrode active material in the form of particles may be, for example, about 10 nm to about 2 μm, about 10 nm to about 1 μm, about 10 nm to about 500 nm, about 10 nm to about 300 nm, about 10 nm to about 200 nm, or about 10 nm to about 100 nm. Within these size ranges, the negative electrode active material can more easily perform reversible insertion and / or extraction of lithium during charging and discharging. The size of the negative electrode active material may be, for example, the average particle size of the negative electrode active material. The average particle size of the negative electrode active material may be, for example, the median particle size (D50) measured using a laser particle size distribution analyzer.

[0075] The aspect ratio of the negative electrode active material may be, for example, about 5 or less, about 4 or less, about 3 or less, or about 2 or less. The aspect ratio of the negative electrode active material may be, for example, about 1 to about 5, about 1 to about 4, about 1 to about 3, or about 1 to about 2. Within these aspect ratio ranges, the negative electrode active material may be more uniformly distributed in the first negative electrode active material layer 22. As a result, the non-uniformity of the volume change of the negative electrode active material during charge and discharge may be suppressed or reduced. The aspect ratio of the negative electrode active material may be measured using, for example, a scanning electron microscope.

[0076] The negative electrode active material included in the first negative electrode active material layer 22 may include, for example, a metal-based negative electrode active material.

[0077] Metal negative electrode active materials include, for example, silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn) or a combination thereof, but are not necessarily limited thereto, and any metal negative electrode active material that can form an alloy or compound with lithium in the art can be used herein. For example, nickel (Ni) does not form an alloy with lithium, so nickel (Ni) is not a metal negative electrode active material.

[0078] For example, the first negative electrode active material layer 22 may not include (eg, exclude) a carbon-based negative electrode active material. Since the first negative electrode active material layer 22 does not contain a carbon-based negative electrode active material, the energy density of the first negative electrode active material layer 22 may be further improved.

[0079] In some embodiments, the first negative electrode active material layer 22 includes a negative electrode active material, and the negative electrode active material may be, for example, a composite negative electrode active material. The composite negative electrode active material may include, for example, a carbon support and a metal negative electrode active material supported on the carbon support. The composite negative electrode active material having such a structure can prevent or reduce the localization of the metal negative electrode active material in the first negative electrode active material layer 22, and can provide a substantially uniform distribution. In this way, the cycle characteristics of the all-solid-state secondary battery 1 including the first negative electrode active material layer 22 can be further improved. The metal negative electrode active material supported on the carbon support may include, for example, silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), tellurium (Te) and zinc (Zn). The carbon support may be, for example, amorphous carbon. Amorphous carbon may include, for example, carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), graphene, activated carbon, etc., but is not necessarily limited thereto, and any carbon classified as amorphous carbon in the relevant technical field may be applied here. Amorphous carbon is carbon that has no crystallinity or has very low crystallinity, and is different from crystalline carbon or graphite-like carbon. The composite negative electrode active material may have, for example, a particle form. The particle size of the composite negative electrode active material having a particle shape may be, for example, about 10 nm to about 2 μm, about 10 nm to about 1 μm, about 10 nm to about 500 nm, about 10 nm to about 200 nm, or about 10 nm to about 100 nm. Within these particle size ranges, reversible insertion and / or extraction of lithium may be promoted during charging and discharging. The metal-based negative electrode active material supported on the support may have, for example, a particle form. The particle size of the metal-based negative electrode active material can be, for example, about 1 nm to about 200 nm, about 1 nm to about 150 nm, about 5 nm to about 100 nm, or about 10 nm to about 50 nm. The carbon-based support can have, for example, a particle form. The particle size of the carbon-based support can be, for example, about 10 nm to about 2 μm, about 10 nm to about 1 μm, about 10 nm to about 500 nm, about 10 nm to about 200 nm, or about 10 nm to about 100 nm. Within these particle size ranges, the carbon-based support can be more uniformly arranged in the first negative electrode active material layer. The carbon-based support can be, for example, a nanoparticle having a particle size of 500 nm or less. The particle size of the composite negative electrode active material, the particle size of the metal-based negative electrode active material, and the particle size of the carbon-based support can be, for example, an average particle size. The average particle size can be, for example, a median particle size (D50) measured using a laser particle size distribution meter. In some embodiments, the average particle size can be automatically determined or manually determined from an electron microscope image using software, for example.

[0080] Negative electrode layer: fibrous carbon material

[0081] The first negative electrode active material layer 22 may further include a fibrous carbon-based material in addition to the negative electrode active material.

[0082] The first negative electrode active material layer 22 may include a mixture of a negative electrode active material capable of forming an alloy or compound with lithium and a fibrous carbon material. For example, the first negative electrode active material layer 22 may include a mixture of a fibrous carbon material and one or more selected from silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn). The weight mixing ratio of the mixture of fibrous carbon materials and silicon, etc. may be, for example, about 99:1 to about 1:99, about 10:1 to about 1:10, about 1:1 to about 1:9, about 1:1 to about 1:8, about 1:1 to about 1:7, about 1:1 to about 1:6, about 1:1 to about 1:5, about 1:1 to about 1:4, or about 1:1 to about 1:3, but it is not necessarily limited to these ranges, and can be changed according to the characteristics required by the all-solid-state secondary battery 1. By using these components of the fibrous carbon-based material and the negative electrode active material, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.

[0083] The first negative electrode active material layer 22 may include a mixture of first particles composed of metal and second particles composed of fibrous carbon materials. The metal may include, for example, silicon (Si), gold (Au), platinum (Pt), palladium (Pd), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn) or a combination thereof. Based on the total weight of the mixture, the content (e.g., amount) of the second particles may be about 1wt% to about 99wt%, about 1wt% to about 70wt%, about 10wt% to about 70wt%, about 11wt% to about 60wt%, about 12wt% to about 50wt%. By utilizing fibrous carbon materials having these content (e.g., amount) ranges, the cycle characteristics of the all-solid-state secondary battery 1 may be further improved.

[0084] In some embodiments, the size of the negative electrode active material that can form an alloy or compound with lithium can be smaller than the length of the fibrous carbon material. Since the length of the fibrous carbon material is greater than the size of the negative electrode active material, the fibrous carbon material can act as a support and / or buffer in multiple negative electrode active materials. The fibrous carbon material can be arranged between multiple negative electrode active materials to effectively relieve the stress caused by the volume change of the negative electrode active material caused by the precipitation and / or dissolution of lithium during charging and discharging. As a result, the volume change of the first negative electrode active material layer 22 during charging and discharging can be more effectively suppressed or reduced. The ratio of the size of the negative electrode active material to the length of the fibrous carbon material can be, for example, about 1:10 to about 1:2000, about 1:10 to about 1:1000, about 1:10 to about 1:500, about 1:10 to about 1:200, about 1:10 to about 1:100, about 1:10 to about 1:50, or about 1:10 to about 1:20. In the above ranges of the ratio of the size of the negative electrode active material to the length of the fibrous carbon-based material, for example, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.

[0085] The fibrous carbon material may be, for example, a conductive carbon material. The conductive fibrous carbon material may provide a conductive path within the first negative electrode active material layer 22. The fibrous carbon material may more effectively reduce the internal resistance of the first negative electrode active material layer 22. As a result, the cycle characteristics of the all-solid-state secondary battery 1 may be improved. In addition to the fibrous carbon material, the first negative electrode active material layer 22 may not include any other carbon conductive material. Since no other carbon conductive material than the fibrous carbon material is present in the first negative electrode active material layer 22, the energy density of the first negative electrode active material layer 22 may be further improved.

[0086] The aspect ratio of the fibrous carbon-based material can be, for example, about 10 or more, about 20 or more, about 30 or more, or about 50 or more. The aspect ratio of the fibrous carbon-based material can be, for example, about 2000 or less, about 1000 or less, about 500 or less, about 200 or less, or about 100 or less. The aspect ratio of the fibrous carbon-based material can be, for example, about 10 to about 2000, about 20 to about 2000, about 30 to about 2000, or about 50 to about 2000. The aspect ratio of the fibrous carbon-based material can be, for example, about 10 to about 2000, about 10 to about 1000, about 10 to about 500, about 10 to about 200, about 10 to about 100, about 10 to about 50, or about 10 to about 20. The aspect ratio of the fibrous carbon-based material can be, for example, the ratio of the length of the major axis of the fibrous carbon-based material (i.e., the length of the fibrous carbon-based material) to the length of the minor axis perpendicular to the major axis (i.e., the diameter of the fibrous carbon-based material). As used herein, "aspect ratio" can refer to an average aspect ratio and can be determined by an SEM image. Within these ranges of the aspect ratio of the fibrous carbon-based material, the fibrous carbon-based material can make the conductive path within the first negative electrode active material layer 22 longer. The fibrous carbon-based material can form a three-dimensional conductive network within the first negative electrode active material layer 22, thereby more effectively reducing the internal resistance of the first negative electrode active material layer 22. As a result, the internal resistance of the all-solid-state secondary battery 1 can be reduced. For example, the high rate characteristics of the all-solid-state secondary battery 1 can be improved.

[0087] The fibrous carbon material may include, for example, an amorphous fibrous carbon material, a crystalline fibrous carbon material, or a combination thereof. By including an amorphous fibrous carbon material in the fibrous carbon material, the side reaction between lithium and the fibrous carbon material can be more effectively suppressed or reduced. By improving the reversibility of the electrode reaction of the all-solid-state secondary battery 1 during charging and discharging, the cycle characteristics of the all-solid-state secondary battery 1 can be improved.

[0088] The diameter of the fibrous carbon-based material may be, for example, about 50 nm or less, about 30 nm or less, about 20 nm or less, or about 10 nm or less. The diameter of the fibrous carbon-based material may be, for example, about 1 nm to about 50 nm, about 1 nm to about 30 nm, or about 1 nm to about 10 nm. Fibrous carbon-based materials having these diameter ranges can effectively reduce the internal resistance of the first negative electrode active material layer 22, and can be easily dispersed in a solvent and / or slurry during the manufacture of the first negative electrode active material layer 22.

[0089] The length of the fibrous carbon-based material may be, for example, about 1000 μm or less, about 100 μm or less, about 50 μm or less, about 10 μm or less, about 5 μm or less, about 2 μm or less, about 1 μm or less, about 500 nm or less, or about 300 nm or less. The length of the fibrous carbon-based material may be, for example, about 100 nm to about 1,000 μm, about 100 nm to about 500 μm, about 100 nm to about 100 μm, about 100 nm to about 50 μm, about 100 nm to about 10 μm, about 100 nm to about 5 μm, about 100 nm to about 2 μm, about 100 nm to about 1 μm, about 100 nm to about 500 nm, or about 100 nm to about 300 nm. The length of the fibrous carbon-based material can be, for example, about 500nm to about 1000μm, about 500nm to about 500μm, about 500nm to about 100μm, about 500nm to about 50μm, about 500nm to about 10μm, about 500nm to about 10μm, about 1μm to about 10μm, or about 2μm to about 8μm. When the length of the fibrous carbon-based material increases, the internal resistance of the electrode can be reduced. In the present disclosure, when the material is spherical or circular, "diameter" refers to the circular diameter or the average circular diameter, and when the material is non-spherical or non-circular, "diameter" refers to the major axis length or the average major axis length.

[0090] The fibrous carbon-based material may include, for example, a fibrous carbon nanostructure, which may include, for example, carbon nanofibers, carbon nanotubes, carbon nanobelts, or a combination thereof.

[0091] The carbon nanotube may include, for example, a carbon nanotube primary structure, a carbon nanotube secondary structure formed by aggregating a plurality of carbon nanotube primary structures, or a combination thereof.

[0092] The primary structure of the carbon nanotube may be a carbon nanotube unit. The carbon nanotube unit has a graphene sheet having a cylindrical shape with a nanometer-sized diameter and sp 2 Bonding structure. Depending on the angle and structure of the graphite surface bending, the characteristics of a conductor or semiconductor can be obtained. According to the number of bonds forming the wall, carbon nanotube units can be classified into single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT). The thinner the wall thickness of the carbon nanotube unit, the lower the resistance.

[0093] The carbon nanotube primary structure may include, for example, single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT) and multi-walled carbon nanotubes (MWCNT), or a combination thereof. The diameter of the carbon nanotube primary structure may be, for example, about 1 nm or more or about 2 nm or more. The diameter of the carbon nanotube primary structure may be, for example, about 20 nm or less or about 10 nm or less. The diameter of the carbon nanotube primary structure may be, for example, about 1 nm to about 20 nm, about 1 nm to about 15 nm, or about 1 nm to about 10 nm. The length of the carbon nanotube primary structure may be, for example, about 100 nm or more or about 200 nm or more. The length of the carbon nanotube primary structure may be, for example, about 2 μm or less, about 1 μm or less, about 500 nm or less, or about 300 nm or less. The length of the carbon nanotube primary structure can be, for example, about 100 nm to about 2 μm, about 100 nm to about 1 μm, about 100 nm to about 500 nm, about 100 nm to about 400 nm, about 100 nm to about 300 nm, or about 200 nm to about 300 nm. The diameter and length of the carbon nanotube primary structure can be measured using a scanning electron microscope (SEM) image or a transmission electron microscope (TEM) image. In some embodiments, the diameter and / or length of the carbon nanotube primary structure can be measured by laser diffraction.

[0094] The carbon nanotube secondary structure can be a structure formed by completely or partially aggregating the carbon nanotube primary structure to form a bundle type (or class) or a rope type (or class). The carbon nanotube secondary structure can include, for example, a bundle type (or class) carbon nanotube, a rope type (or class) carbon nanotube, or a combination thereof. The diameter of the carbon nanotube secondary structure can be, for example, about 2nm or more or about 3nm or more. The diameter of the carbon nanotube secondary structure can be, for example, about 50nm or less, about 30nm or less, about 20nm or less, or about 10nm or less. The diameter of the carbon nanotube secondary structure can be, for example, about 2nm to about 50nm, about 2nm to about 30nm, or about 2nm to about 20nm. The length of the carbon nanotube secondary structure can be, for example, about 500nm or more, about 700nm or more, about 1μm or more, or about 10μm or more. The length of the carbon nanotube secondary structure can be, for example, less than about 1000μm, less than about 500μm, or less than about 100μm. The length of the carbon nanotube secondary structure can be, for example, about 500 nm to about 1000 μm, about 500 nm to about 500 μm, about 500 nm to about 200 μm, about 500 nm to about 100 μm, about 500 nm to about 50 μm, about 500 nm to about 10 μm, about 1 μm to about 10 μm, or about 2 μm to about 8 μm. The diameter and length of the carbon nanotube secondary structure can be measured using an SEM image or an optical microscope image. In some embodiments, the diameter and / or length of the carbon nanotube secondary structure can be measured by laser diffraction.

[0095] In some embodiments, the carbon nanotube secondary structure may be converted into a carbon nanotube primary structure by dispersing it in a solvent and then used to manufacture the first negative active material layer 22 .

[0096] Negative electrode layer: Binder

[0097] In addition to the negative electrode active material and the fibrous carbon material, the first negative electrode active material layer 22 may further include a binder. The binder may be, for example, a polymer binder. The binder included in the first negative electrode active material layer 22 may be, for example, a binder containing polar functional groups. In the binder containing polar functional groups, the polar functional groups include, for example, carboxyl groups, hydroxyl groups, amide groups, aldehyde groups, or combinations thereof. The polar functional groups may be partially or completely replaced by lithium. The polar functional groups may include, for example, lithium-substituted or unsubstituted carboxyl groups, lithium-substituted or unsubstituted hydroxyl groups, lithium-substituted or unsubstituted amide groups, lithium-substituted or unsubstituted aldehyde groups, or combinations thereof. The binder may include, for example, polyacrylic acid, lithium-substituted polyacrylic acid, or combinations thereof. The degree of substitution of lithium in lithium-substituted polyacrylic acid may be, for example, from about 0.1 to about 1.0. The degree of substitution of lithium may be the ratio of the carboxyl group substituted by lithium to the carboxyl group (-COOH) and the lithium-substituted carboxyl group (-COOLi) included in the polyacrylic acid.

[0098] The polymer of the polymer binder may include, for example, polyacrylic acid represented by Formula 1:

[0099] Formula 1

[0100]

[0101] in,

[0102] R 1 , R 2 and R 3 Can be hydrogen, halogen, C1 to C10 alkyl that is not substituted or substituted with halogen, C2 to C10 alkenyl that is not substituted or substituted with halogen, C2 to C10 alkynyl that is not substituted or substituted with halogen, C5 to C10 cycloalkyl that is not substituted or substituted with halogen, C6 to C20 aryl that is not substituted or substituted with halogen, or C2 to C20 heteroaryl that is not substituted or substituted with halogen, M is hydrogen or lithium, n is the degree of polymerization, and can be about 10 to about 10000. The weight average molecular weight of the polymer can be, for example, about 1,000 Daltons to about 250,000 Daltons or about 10,000 Daltons to about 200,000 Daltons. The weight average molecular weight of the polymer can be measured, for example, by gel permeation chromatography (GPC) using polystyrene standard samples.

[0103] Since the lithium-substituted polar functional group is included in the binder, the ionic conductivity of the first negative electrode active material layer 22 including the binder can be further improved. For example, the internal resistance of the first negative electrode active material layer 22 including the binder including the lithium-substituted polar functional group can be lower than the internal resistance of the first negative electrode active material layer 22 including the binder not including the lithium-substituted polar functional group. As a result, the cycle characteristics of the all-solid-state secondary battery 1 including the first negative electrode active material layer 22 including the binder containing the lithium-substituted polar functional group can be improved.

[0104] The first negative electrode active material layer 22 may further include other binders. The first negative electrode active material layer 22 may further include other binders, and the other binders may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polyvinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but are not necessarily limited thereto, and any binder used as a binder in the art may be used here.

[0105] Since the binder is included in the first negative active material layer 22, the first negative active material layer 22 is stable on the negative current collector 21. In some embodiments, despite the volume change and / or relative position change of the first negative active material layer 22 during the charge and discharge process, cracking of the first negative active material layer 22 is suppressed or reduced. For example, if (for example, when) the first negative active material layer 22 does not include a binder, the first negative active material layer 22 may be easily separated from the negative current collector 21. At the portion of the negative current collector 21 exposed due to the separation of the first negative active material layer 22 from the negative current collector 21, the negative current collector 21 may contact the solid electrolyte layer 30, resulting in a high probability of short circuit. The first negative active material layer 22 can be manufactured by, for example, applying a slurry in which a material constituting the first negative active material layer 22 is dispersed onto the negative current collector 21 and drying it. Since the binder is included in the first negative active material layer 22, the negative active material and the fibrous carbon-based material can be stably dispersed in the slurry. For example, if (eg, when) the slurry is applied to the negative electrode collector 21 by screen printing, clogging of the screen (eg, clogging caused by aggregates of the negative electrode active material) may be suppressed or reduced.

[0106] Based on 100 parts by weight of the negative electrode active material, the binder content (e.g., amount) can be about 0.1 parts by weight to about 20 parts by weight, about 0.1 parts by weight to about 15 parts by weight, about 1 part by weight to about 10 parts by weight, or about 5 parts by weight to about 10 parts by weight. Within the range of these binder contents (e.g., amounts), the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.

[0107] Negative electrode layer: other additives

[0108] The first negative electrode active material layer 22 may further include additives used in all-solid-state secondary batteries of the related art, and examples of such additives are fillers, coating agents, dispersants, and ion conduction aids.

[0109] Negative electrode layer: first negative electrode active material layer

[0110] The initial charge capacity (B) of the first negative electrode active material layer 22 can be, for example, about 75% or less, about 70% or less, about 60% or less, about 50% or less, about 40% or less, about 30% or less, about 20% or less, or about 10% or less of the initial charge capacity (A) of the positive electrode active material layer 12.

[0111] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer 22 to the initial charge capacity (A) of the positive electrode active material layer 12 may be, for example, about 0.01 to about 0.75, about 0.01 to about 0.7, about 0.01 to about 0.6, about 0.01 to about 0.5, about 0.01 to about 0.4, about 0.01 to about 0.3, about 0.01 to about 0.2, or about 0.01 to about 0.1. The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer 22 to the initial charge capacity (A) of the positive electrode active material layer 12 may be, for example, about 0.05 to about 0.75, about 0.1 to about 0.7, about 0.1 to about 0.6, about 0.2 to about 0.6, about 0.2 to about 0.5, or about 0.2 to about 0.45. The initial charge capacity of the positive electrode active material layer 12 can be calculated by charging from the first open circuit voltage to the maximum charge voltage vs. Li / Li + The initial charge capacity of the first negative electrode active material layer 22 is determined by charging from the second open circuit voltage to about 0.01 V vs. Li / Li + The maximum charge voltage depends on the type or kind of the positive electrode active material. The maximum charge voltage can be, for example, about 1.5V, about 2.0V, about 2.5V, about 3.0V, about 3.5V, about 4.0V, about 4.2V, or about 4.3V. For example, Li 2 S or Li 2 The maximum charge voltage of the S complex can be determined to be about 2.5 V vs. Li / Li + About 3.0V vs.Li / Li + For example, the maximum charge voltage of lithium transition metal oxides can be determined to be about 3.0 V vs. Li / Li + About 4.5V vs.Li / Li + between.

[0112] The initial charge capacity (mAh) of the positive electrode active material layer 12 can be obtained by multiplying the charge specific capacity (mAh / g) of the positive electrode active material by the mass (g) of the positive electrode active material in the positive electrode active material layer 12. If (for example, when) several types (kinds) of positive electrode active materials are used, the equation of charge capacity density × mass value is applied to each positive electrode active material, and the sum of these values ​​is the initial charge capacity of the positive electrode active material layer 12. The initial charge capacity of the first negative electrode active material layer 22 is also calculated in substantially the same manner. The initial charge capacity of the first negative electrode active material layer 22 can be obtained by multiplying the charge specific capacity (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the first negative electrode active material layer 22. If (for example, when) several types (kinds) of negative electrode active materials are used, the equation of charge capacity density × mass value is applied to each negative electrode active material, and the sum of these values ​​is the initial charge capacity of the first negative electrode active material layer 22. The charge capacity of each of the positive electrode active material and the negative electrode active material can be measured using an all-solid-state half-cell using lithium metal as a counter electrode. The initial charge capacity of each of the positive electrode active material layer 12 and the first negative electrode active material layer 22 can be measured using an all-solid-state half-cell at a constant current density (e.g., about 0.1 mA / cm 2 For the positive electrode active material layer, the charge voltage can be directly measured from the first open circuit voltage (OCV) to the maximum charge voltage (e.g., about 3.0 V (vs. Li / Li + ) is measured at an operating voltage of about 0.1 mA / cm . For the first negative electrode active material layer, the measurement can be performed from the second open circuit voltage (OCV) to an operating voltage of about 0.01 V relative to the negative electrode (e.g., lithium metal). For example, an all-solid-state half-cell having a positive electrode active material layer can be measured at about 0.1 mA / cm 2 The all-solid-state half-battery having the first negative active material layer can be charged at a constant current of about 0.1 mA / cm 2 The constant current during the constant current charging can be, for example, about 0.2 mA / cm 2 or about 0.5mA / cm 2 The all-solid-state half-cell having the positive active material layer can be charged from, for example, the first open circuit voltage to about 2.5 V, about 3.0 V, about 3.5 V, about 4.0 V, or about 4.5 V. The maximum charge voltage of the positive active material layer can be determined by the maximum voltage of the battery that satisfies the safety conditions according to the Japanese Standards Association JIS C8712:2015.

[0113] If (for example, when) the initial charge capacity of the first negative electrode active material layer 22 is too small, the thickness of the first negative electrode active material layer 22 becomes very small, so that the lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 may cause the first negative electrode active material layer 22 to collapse. In this case, it may be difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If (for example, when) the charge capacity of the first negative electrode active material layer 22 is excessively increased, the energy density of the all-solid-state secondary battery 1 may be reduced, and the internal resistance of the all-solid-state secondary battery 1 caused by the first negative electrode active material layer 22 may be increased. Therefore, it may be difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.

[0114] The thickness of the first negative electrode active material layer 22 may be, for example, about 50% or less, about 40% or less, about 30% or less, about 20% or less, or about 10% or less of the thickness of the positive electrode active material layer 12. The thickness of the first negative electrode active material layer 22 may be, for example, about 1% to about 50%, about 1% to about 40%, about 1% to about 30%, about 1% to about 20%, or about 1% to about 10% of the thickness of the positive electrode active material layer 12. The thickness of the first negative electrode active material layer 22 may be, for example, about 1 μm to about 50 μm, about 2 μm to about 40 μm, about 3 μm to about 30 μm, about 4 μm to about 20 μm, or about 5 μm to about 20 μm. The thickness of the first negative electrode active material layer 22 may be, for example, about 5 μm to about 50 μm, about 10 μm to about 50 μm, about 15 μm to about 50 μm, about 20 μm to about 50 μm, or about 25 μm to about 50 μm. If (for example, when) the thickness of the first negative electrode active material layer 22 is too small, the lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 may collapse the first negative electrode active material layer 22. Therefore, it may be difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If (for example, when) the thickness of the first negative electrode active material layer 22 is excessively increased, the energy density of the all-solid-state secondary battery 1 may be reduced, and the internal resistance of the all-solid-state secondary battery 1 caused by the first negative electrode active material layer 22 may be increased. Therefore, it may be difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. For example, if (for example, when) the thickness of the first negative electrode active material layer 22 is reduced, the initial charge capacity of the first negative electrode active material layer 22 may also be reduced.

[0115] Negative electrode layer: second negative electrode active material layer

[0116] Reference Figure 3, after charging, the all-solid-state secondary battery 1 may further include, for example, a second negative electrode active material layer 24 disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 or between the first negative electrode active material layer 22 and the solid electrolyte layer 30. The second negative electrode active material layer 24 may be a metal layer containing lithium or a lithium alloy. The metal layer may include lithium or a lithium alloy. Therefore, since the second negative electrode active material layer 24 is a metal layer containing lithium, the second negative electrode active material layer 24 may act as, for example, a lithium storage member. Lithium alloys include, for example, Li-Al alloys, Li-Sn alloys, Li-In alloys, Li-Ag alloys, Li-Au alloys, Li-Zn alloys, Li-Ge alloys, Li-Si alloys, etc., but are not limited thereto, and any lithium alloy used in the relevant technical field may be applied here. The second negative electrode active material layer 24 may include one of these alloys or lithium (e.g., composed of one of these alloys or lithium), or may include several types (kinds) of alloys (e.g., composed of several types (kinds) of alloys). The second negative electrode active material layer 24 may be, for example, a plated layer. For example, the second negative electrode active material layer 24 may be plated between the first negative electrode active material layer 22 and the negative electrode collector 21 during the charging process of the all-solid-state secondary battery 1 .

[0117] The thickness of the second negative electrode active material layer 24 is not limited to but may be, for example, about 1 μm to about 200 μm, about 1 μm to about 150 μm, about 1 μm to about 100 μm, about 1 μm to about 50 μm, about 1 μm to about 30 μm, about 1 μm to about 22 μm, or about 1 μm to about 10 μm. If (for example, when) the thickness of the second negative electrode active material layer 24 is too small, the second negative electrode active material layer 24 is difficult to use as a lithium storage member. If (for example, when) the thickness of the second negative electrode active material layer 24 is too large, the mass and volume of the all-solid-state secondary battery 1 may be increased, and the cycle characteristics of the all-solid-state secondary battery 1 may actually be degraded.

[0118] For example, the thickness of the second negative electrode active material layer 24 may be less than the thickness of the first negative electrode active material layer 22. The thickness of the second negative electrode active material layer 24 may be, for example, about 70% or less, about 60% or less, about 50% or less, about 40% or less, or about 30% or less of the thickness of the first negative electrode active material layer 22. The thickness of the second negative electrode active material layer 24 may be, for example, about 1% to about 70%, about 1% to about 60%, about 1% to about 50%, about 1% to about 40%, or about 1% to about 30% of the thickness of the first negative electrode active material layer 22. Since the thickness of the second negative electrode active material layer 24 is less than the thickness of the first negative electrode active material layer 22, the volume change of the all-solid-state secondary battery during charging and discharging can be suppressed or reduced. As a result, since the volume change of the all-solid-state secondary battery is suppressed, the above-mentioned degradation can be suppressed or reduced.

[0119] In some embodiments, the second negative electrode active material layer 24 of the all-solid-state secondary battery 1 may be disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1. If (for example, when) the second negative electrode active material layer 24 is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1, since the second negative electrode active material layer 24 is a metal layer including lithium, the second negative electrode active material layer 24 may be used as a lithium storage member. For example, a lithium foil may be placed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1.

[0120] If (for example, when) the second negative electrode active material layer 24 is plated by charging after assembling the all-solid-state secondary battery 1, the energy density of the all-solid-state secondary battery 1 can be increased because the second negative electrode active material layer 24 is not included during the assembly of the all-solid-state secondary battery 1. When the all-solid-state secondary battery 1 is charged, the charging capacity of the first negative electrode active material layer 22 may be exceeded. For example, the first negative electrode active material layer 22 may be overcharged. In the early stage of charging, lithium is embedded in the first negative electrode active material layer 22. The negative electrode active material included in the first negative electrode active material layer 22 may form an alloy or compound with lithium ions that have migrated from the positive electrode layer 10. For example, if (for example, when) charging exceeds the capacity of the first negative electrode active material layer 22, lithium is plated on the rear surface of the first negative electrode active material layer 22 (that is, between the negative electrode collector 21 and the first negative electrode active material layer 22), and a metal layer corresponding to the second negative electrode active material layer 24 may be formed by the plated lithium. The second negative electrode active material layer 24 may be a metal layer mainly composed of lithium (ie, metallic lithium). This result is obtained by, for example, including a material that forms an alloy or compound with lithium in the negative electrode active material included in the first negative electrode active material layer 22. During discharge, the lithium in the first negative electrode active material layer 22 and the second negative electrode active material layer 24 (ie, the metal layer) is ionized and moves toward the positive electrode layer 10. Therefore, in the all-solid-state secondary battery 1, lithium can be used as a negative electrode active material. In some embodiments, since the first negative electrode active material layer 22 covers the second negative electrode active material layer 24, the first negative electrode active material layer 22 can act as a protective layer for the second negative electrode active material layer 24 (ie, the metal layer), while suppressing or reducing the precipitation growth of lithium dendrites. Therefore, the short circuit and capacity reduction of the all-solid-state secondary battery 1 are suppressed or reduced, and as a result, the cycle characteristics of the all-solid-state secondary battery 1 are improved. In some embodiments, if (for example, when) the second negative electrode active material layer 24 is set by charging after assembling the all-solid-state secondary battery 1, the negative electrode layer 20 (i.e., the negative electrode current collector 21 and the first negative electrode active material layer 22 and the area therebetween) can be a lithium-free (Li) region that does not contain lithium in the initial state or fully discharged state of the all-solid-state secondary battery 1.

[0121] Negative electrode layer: negative electrode current collector

[0122] The negative electrode current collector 21 may include, for example, a material that does not react with lithium (i.e., does not form any alloy or compound with lithium). The materials constituting the negative electrode current collector 21 include, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), and nickel (Ni), but are not necessarily limited thereto, and any material used as an electrode current collector in the art may be applied here. The negative electrode current collector 21 may include one of the above metals, or an alloy or coating material of two or more of the above metals (e.g., composed of one of the above metals, or an alloy or coating material of two or more of the above metals). The negative electrode current collector 21 may be, for example, in the form of a sheet or foil.

[0123] Reference Figure 2 , the all-solid-state secondary battery 1 may further include a thin film 23 containing an element capable of forming an alloy with lithium on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the negative electrode current collector 21. The thin film 23 may be disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22. The thin film 23 may include, for example, an element capable of forming an alloy with lithium. Elements capable of forming an alloy with lithium include, for example, gold, silver, zinc, tin, indium, silicon, aluminum, and bismuth, but are not necessarily limited thereto, and any element capable of forming an alloy with lithium in the art may be applied here. The thin film 23 may include an alloy of one of these metals or several types (kinds) of these metals (e.g., composed of an alloy of one of these metals or several types (kinds) of these metals). For example, since the thin film 23 is placed on at least one side (for example, one side or both sides (for example, opposite sides)) of the negative electrode collector 21, the plating morphology of the second negative electrode active material layer 24 plated between the thin film 23 and the first negative electrode active material layer 22 can be made flatter, and the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.

[0124] The thickness of the film 23 may be, for example, about 1 nm to about 800 nm, about 10 nm to about 700 nm, about 50 nm to about 600 nm, or about 100 nm to about 500 nm. If (for example, when) the thickness of the film 23 is less than 1 nm, the film 23 may be difficult to perform its function. If (for example, when) the thickness of the film 23 is too large, the film 23 itself may be constructed to adsorb lithium, so the amount of lithium plated at the negative electrode layer may be reduced, thereby reducing the energy density of the all-solid-state secondary battery 1 and reducing the cycle characteristics of the all-solid-state secondary battery 1. The film 23 can be arranged on the negative electrode current collector 21 by, for example, vacuum deposition, sputtering, electroplating, etc., but the method for forming the film 23 is not necessarily limited to these methods, and any method capable of forming a film in the art can be used here.

[0125] In some embodiments, the negative electrode current collector 21 may include, for example, a base film and a metal layer disposed on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The polymer may be an insulating polymer. If (e.g., when) the base film includes an insulating thermoplastic polymer, if (e.g., when) a short circuit occurs, the base film softens or liquefies and blocks the battery operation, thereby suppressing the rapid increase in current. The metal layer may include, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The negative electrode current collector 21 may additionally include a metal sheet and / or a lead tab. For more detailed information about the negative electrode current collector 21, the base layer, metal layer, metal sheet and lead tab of the negative electrode current collector 21 can be understood with reference to the positive electrode current collector. By having such a structure, the negative electrode current collector 21 can help reduce the weight of the negative electrode layer, thereby improving the energy density of the negative electrode layer and the lithium battery.

[0126] Negative electrode layer: first inert component

[0127] Reference Figures 4 to 5 and Figures 8 to 12 The all-solid-state secondary battery 1 may further include a first inert member 40 , 40 a , 40 b disposed on one or more of the other side of the negative electrode collector 21 and the other side of the positive electrode collector 11 .

[0128] The first inert member 40, 40a, 40b may not include (eg, may exclude) the electrode active material. The first inert member 40, 40a, 40b may be, for example, an insulating member.

[0129] The first inert member 40, 40a, 40b may have conductivity by additionally including a conductive material. By additionally including a flame retardant material, the first inert member 40, 40a, 40b may be, for example, a flame retardant inert member.

[0130] The first inert member 40, 40a, 40b may be, for example, an elastic member. The first inert member 40, 40a, 40b may be, for example, a porous elastic member. The first inert member 40, 40a, 40b may be, for example, an elastic member having one or more of porosity, conductivity, and flame retardancy.

[0131] The first inert member 40, 40a, 40b can provide a buffer function to the all-solid secondary battery 1. The first inert member 40, 40a, 40b can provide, for example, stress relaxation and restoring force. The first inert member 40, 40a, 40b can effectively allow the volume change of the all-solid secondary battery 1 and can apply a constant pressure to the all-solid secondary battery 1.

[0132] The first inert member 40, 40a, 40b may have, for example, an elastic modulus lower than that of the negative electrode current collector 21. Since the elastic modulus of the first inert member 40, 40a, 40b is lower than that of the negative electrode current collector 21, the volume change of the negative electrode layer 20 during the charge and discharge of the all-solid-state secondary battery 1 may be more effectively tolerated. The first inert member 40, 40a, 40b may effectively reduce the internal stress caused by the volume change of the all-solid-state secondary battery 1 during the charge and discharge of the all-solid-state secondary battery 1, thereby improving the cycle characteristics of the all-solid-state secondary battery 1.

[0133] In some embodiments, the first inert member 40, 40a, 40b may be placed on the negative electrode layer 20 of the all-solid-state secondary battery 1. If (for example, when) the volume change of the negative electrode layer 20 during charging and discharging of the all-solid-state secondary battery 1 is relatively large compared to the positive electrode layer 10 and the solid electrolyte layer 30, the volume change of the negative electrode layer 20 may be more effectively tolerated because the first inert member 40, 40a, 40b is positioned adjacent to the negative electrode layer 20. In some embodiments, the first inert member 40, 40a, 40b may induce substantially uniform plating of lithium metal in the negative electrode layer 20 by applying a certain pressure to the negative electrode layer 20. Therefore, defects formed in the all-solid-state secondary battery 1 due to uneven plating of lithium metal may be effectively prevented or reduced.

[0134] In some embodiments, the first inert member 40, 40a, 40b may be disposed on the positive electrode layer 10 of the all-solid-state secondary battery 1. By positioning the first inert member 40, 40a, 40b adjacent to the positive electrode layer 10, the volume change of the all-solid-state secondary battery 1 may be more effectively tolerated. In some embodiments, the first inert member 40, 40a, 40b applies a constant pressure to the all-solid-state secondary battery 1 to induce substantially uniform plating of lithium metal in the negative electrode layer 20. Thus, defects formed in the all-solid-state secondary battery 1 due to uneven plating of lithium metal may be effectively prevented or reduced.

[0135] The first inertial member 40,40a,40b may include a polymer material, a rubber material or a combination thereof. The first inertial member 40,40a,40b may have stress release and elasticity by including a polymer material, a rubber material or a combination thereof. The polymer material may include, for example, a polyurethane polymer, a polyacrylic polymer, a polystyrene polymer, a polyester polymer, a polyamide polymer, a polyolefin polymer or a combination thereof. The polymer material may be, for example, a polymer resin. The polymer material may, for example, be an adhesive resin. The rubber material may include, for example, natural rubber (NR), butadiene rubber (BR), nitrile rubber, silicone rubber, isoprene rubber (IR), styrene-butadiene rubber (SBR), isoprene-butadiene rubber, styrene-isoprene-butadiene rubber, acrylonitrile-butadiene rubber (NBR), ethylene-propylene-diene rubber, halogenated butyl rubber, chloroprene (CR), halogenated isoprene rubber, halogenated isobutylene copolymer, chloroprene rubber, butyl rubber (IIR), halogenated isobutylene-p-methylstyrene rubber or a combination thereof. Polyurethane polymers may include, for example, polyester polyurethane, polyether polyurethane or a combination thereof. Polyacrylic polymers may include, for example, polyacrylate, polymethyl acrylate, polymethacrylate, polymethyl methacrylate or a combination thereof. Polystyrene polymers may include, for example, styrene-ethylene-butylene copolymer (SEB), styrene-butadiene-styrene copolymer (SBS), hydrogenated products of SBS (styrene-ethylene-butylene-styrene copolymer (SEBS)), styrene-isoprene-styrene copolymer (SIS), hydrogenated products of SIS (styrene-ethylene-propylene-styrene copolymer (SEPS)), styrene-isobutylene-styrene copolymer (SIBS), styrene-butadiene-styrene-butadiene copolymer (SBSB), styrene-butadiene-styrene-butadiene-styrene copolymer (SBSBS), polystyrene (PS), acrylonitrile styrene copolymer (AS), acrylonitrile butadiene styrene copolymer (ABS) or a combination thereof. Polyester polymers may include, for example, polyethylene terephthalate, polybutylene terephthalate or a combination thereof. The polyamide-based polymer may include, for example, polyamide 6, polyamide 11, polyamide 12, polyamide 66, polyamide 610, or a combination thereof.Polyolefin polymers may include, for example, polyethylene, polypropylene, ethylene propylene copolymer, propylene-1-hexene copolymer, propylene-4-methyl-1-pentene copolymer, propylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-4-methyl-pentene copolymer, ethylene-1-butene copolymer, 1-butene-1-hexene copolymer, 1-butene-4-methyl-pentene copolymer, ethylene methacrylic acid copolymer, ethylene ethyl methacrylate copolymer, ethylene butyl methacrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, propylene-methacrylic acid copolymer, propylene-methyl methacrylate copolymer, propylene-ethyl methacrylate copolymer, propylene-butyl methacrylate copolymer, propylene-methyl acrylate copolymer, propylene-ethyl acrylate copolymer, propylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer (EVA), propylene vinyl acetate copolymer, or combinations thereof.

[0136] The first inertial member 40, 40a, 40b may include, for example, porous foam, porous sponge or a combination thereof. The first inertial member 40, 40a, 40b may include, for example, a porous foam sheet, a porous sponge sheet or a combination thereof. Due to these structures, the first inertial member 40, 40a, 40b may provide porosity and cushioning functions. The porous foam may include, for example, a closed cell, an open cell or a combination thereof. The porous sponge may include, for example, a closed cell, an open cell or a combination thereof. The closed cell refers to a mouth or hole (for example, a closed cell) that is not connected to the surrounding (for example, the periphery) atmosphere. The open cell refers to a mouth or hole (for example, an open cell) that is connected to the surrounding (for example, the periphery) atmosphere. The first inertial member 40, 40a, 40b may include, for example, a closed porous foam, an open porous foam, a closed porous sponge, an open porous sponge or a combination thereof. The porous foam may include, for example, both closed and open (for example, both closed and open may be included simultaneously). The porous sponge may include, for example, both closed cells and open cells (eg, may include, for example, both closed cells and open cells at the same time).

[0137] The first inert member 40,40a,40b can include, for example, a conductive material. Conductive material can be, for example, graphite, carbon black, acetylene black, Ketjen black, conductive acetylene black, carbon fiber, carbon nanotube (CNT), graphene, metal fiber, metal powder, etc. Based on 100 weight portions of the first inert member 40,40a,40b, the content (for example, amount) of the conductive material included in the first inert member 40,40a,40b can be, for example, about 1 weight portion to about 40 weight portions, about 1 weight portion to about 30 weight portions, about 1 weight portion to about 20 weight portions, about 1 weight portion to about 15 weight portions, about 1 weight portion to about 10 weight portions, about 5 weight portions to about 40 weight portions, about 5 weight portions to about 30 weight portions, or about 5 weight portions to about 35 weight portions. If (for example, when) the first inert member 40,40a,40b has conductivity (for example, being a conductor), the first inert member 40,40a,40b can be used as a negative electrode current collector.

[0138] The first inert member 40, 40a, 40b may include, for example, a matrix and a filler. The matrix may include, for example, a base material and a reinforcing material. The matrix may include, for example, a fibrous base material and a fibrous reinforcing material. By including the fibrous base material, the matrix may have elasticity. The fibrous base material may include, for example, one or more selected from pulp fibers, insulating polymer fibers, and ion conductive polymer fibers. Due to the inclusion of the reinforcing material, the matrix may have enhanced strength. The fibrous reinforcing material may include, for example, glass fibers, metal oxide fibers, and ceramic fibers. The fibrous reinforcing material may be, for example, a flame retardant material. The filler may be, for example, a hygroscopic agent and / or a flame retardant. The filler may be, for example, a metal hydroxide having moisture adsorption properties. The metal hydroxide contained in the filler may be, for example, Mg(OH) 2 、Fe(OH) 3 、Sb(OH) 3 、Sn(OH) 4 TI(OH) 3 、Zr(OH) 4 、Al(OH) 3 or a combination thereof.

[0139] In some embodiments, the thickness of the first inert member 40, 40a, 40b may be greater than the thickness of the first negative active material layer 22. Since the first inert member 40, 40a, 40b has a thickness greater than the thickness of the first negative active material layer 22, the volume change of the negative electrode layer 20 during charging and discharging can be more effectively allowed. The thickness of the first negative active material layer 22 may be about 50% or less, about 40% or less, about 30% or less, about 20% or less, or about 10% or less of the thickness of the first inert member 40, 40a, 40b. The thickness of the first negative active material layer 22 may be, for example, about 1% to about 50%, about 1% to about 40%, about 1% to about 30%, about 1% to about 20%, or about 1% to about 10% of the thickness of the first inert member 40, 40a, 40b. The thickness of the first inert member 40, 40a, 40b can be, for example, about 10 μm to about 300 μm, about 20 μm to about 300 μm, about 50 μm to about 300 μm, or about 100 μm to about 200 μm. If (for example, when) the thickness of the first inert member 40, 40a, 40b is too thin, the expected effect may not be provided, and if (for example, when) the thickness of the first inert member 40, 40a, 40b is too thick, the energy density of the all-solid-state secondary battery 1 may be reduced. The shape of the first inert member 40, 40a, 40b is not limited and can be selected according to the shape of the all-solid-state secondary battery 1. The first inert member 40, 40a, 40b can be (for example, including) a sheet form, a rod form or a washer form. In some embodiments, the first inert member 40, 40a, 40b may not be provided.

[0140] Positive electrode layer

[0141] Positive electrode layer: positive electrode active material

[0142] Reference Figures 1 to 12 The positive electrode active material layer 12 may include, for example, a positive electrode active material.

[0143] The positive active material included in the positive active material layer 12 may be a positive active material that can reversibly intercalate and deintercalate lithium ions. The positive active material may include, for example, an oxide-based positive active material, a sulfide-based positive active material, or a combination thereof.

[0144] The oxide-based positive electrode active material may include, for example, lithium transition metal oxides, lithium-free metal oxides, or combinations thereof. The lithium transition metal oxide may include, for example, lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium manganate, lithium iron phosphate, or combinations thereof. The lithium-free metal oxide may include, for example, iron oxide, vanadium oxide, or combinations thereof.

[0145] Sulfide-based positive electrode active materials may include, for example, nickel sulfide, copper sulfide, Li 2 S, Li 2 S complex or a combination thereof.

[0146] The oxide-based positive electrode active material may be, for example, a composite oxide of lithium and one or more types (species) of metals selected from cobalt, manganese, nickel, and combinations thereof. The lithium-containing oxide-based positive electrode active material may include, for example, a compound represented by one of the following: Li a A 1-b B' b D 2 (where 0.90≤a≤1, and 0≤b≤0.5); Li a E 1-b B' b O 2-c D c (where 0.90≤a≤1, 0≤b≤0.5, and 0≤c≤0.05); LiE 2-b B' b O 4-c D c (where 0≤b≤0.5, and 0≤c≤0.05); Li a Ni 1-b-c Co b B' c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b- c Co b B' c O 2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Mn b B' c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2); Li a Ni 1-b-c Mn b B' c O 2-α F'α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c O 2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05); Li a Ni b E c G d O 2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O 2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1); Li a NeG b O 2 (where 0.90≤a≤1, and 0.001≤b≤0.1); Li a CoG b O 2 (where 0.90≤a≤1, and 0.001≤b≤0.1); Li a MnG b O 2 (where 0.90≤a≤1, and 0.001≤b≤0.1); Li a Mn 2 G b O 4 (where 0.90≤a≤1, and 0.001≤b≤0.1); LiV 2 O 5 ;LiI'O 2 ;LiNiVO 4 ;Li (3-f) J 2 (PO 4 ) 3 (where 0≤f≤2); Li (3-f) Fe 2 (PO 4 ) 3 (where 0≤f≤2); and LiFePO 4 .

[0147] In the formulas representing these compounds, A can be Ni, Co, Mn, or a combination thereof; B' can be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D can be O, F, S, P, or a combination thereof; E can be Co, Mn, or a combination thereof; F' can be F, S, P, or a combination thereof; G can be Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; I' can be Cr, V, Fe, Sc, Y, or a combination thereof; and J can be V, Cr, Mn, Co, Ni, Cu, or a combination thereof. Compounds with a coating layer provided on their surfaces can be utilized, and mixtures of these compounds with compounds having a coating layer can also be utilized. The coating layer provided on the surfaces of these compounds can include coating element compounds such as oxides of the coating element, hydroxides of the coating element, hydroxyoxides of the coating element, carbonate oxides of the coating element, or hydroxycarbonates of the coating element. The compounds constituting the coating layer can be amorphous or crystalline. The coating elements included in the coating layer can be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The method for forming the coating layer can be selected within a range that has no adverse effect on the physical properties of the positive electrode active material. The coating method can be, for example, spraying, dipping method, etc. Since those skilled in the art can well understand the coating method, a detailed description of the coating method will not be provided.

[0148] Oxide-based positive electrode active materials can include, for example, lithium transition metal oxides represented by Formulas 1 to 8:

[0149] Formula 1

[0150] Li a Ni x Co y M z O 2-b A b

[0151] Wherein, in Formula 1,

[0152] 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.8 ≤ x < 1, 0 ≤ y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z = 1,

[0153] M can be manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof, and

[0154] A can be F, S, Cl, Br, or a combination thereof,

[0155] Formula 2

[0156] LiNi x Co y Mn z O 2 ,

[0157] Formula 3

[0158] LiNi x Co y Al z O 2 ,

[0159] wherein, in Formula 2 and Formula 3, 0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, and x + y + z = 1, Formula 4

[0160] LiNi x Co y Mn z Al w O 2

[0161] wherein, in Formula 4, 0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and x + y + z + w = 1, Formula 5

[0162] Li a Co x M y O 2-b A b

[0163] wherein, in Formula 5,

[0164] 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.9 ≤ x ≤ 1, 0 ≤ y ≤ 0.1, and x + y = 1,

[0165] M can be manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof, and

[0166] A can be F, S, Cl, Br, or a combination thereof,

[0167] Formula 6

[0168] Li a Ni x Mn y M' z O2-b A b

[0169] Among them, in Formula 6,

[0170] 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0 < x ≤ 0.3, 0.5 ≤ y < 1, 0 < z ≤ 0.3, and x + y + z = 1,

[0171] M' is cobalt (Co), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, and

[0172] A can be F, S, Cl, Br or a combination thereof,

[0173] Formula 7

[0174] Li a M1 x M2 y PO 4-b X b

[0175] Among them, in Formula 7, 0.90 ≤ a ≤ 1.1, 0 ≤ x ≤ 0.9, 0 ≤ y ≤ 0.5, 0.9 < x + y < 1.1, and 0 ≤ b ≤ 2,

[0176] M1 can be chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr) or a combination thereof, and

[0177] M2 can be magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), zinc (Zn), boron (B), niobium (Nb), gallium (Ga), indium (In), molybdenum (Mo), tungsten (W), aluminum (Al), silicon (Si), chromium (Cr), vanadium (V), scandium (Sc), yttrium (Y) or a combination thereof, and X can be O, F, S, P or a combination thereof.

[0178] Formula 8

[0179] Li a M3 z PO 4

[0180] Among them, in Formula 8, 0.90 ≤ a ≤ 1.1, and 0.9 ≤ z ≤ 1.1, and

[0181] M3 can be chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zirconium (Zr) or a combination thereof.

[0182] The oxide-based positive electrode active material may be covered with a coating layer. The coating layer may be any coating layer suitable as a coating layer for a positive electrode active material for an all-solid-state secondary battery. The coating layer may be, for example, Li 2 O-ZrO 2 (LZO).

[0183] The size of the oxide-based positive active material may be, for example, about 0.1 μm to about 30 μm, about 0.5 μm to about 20 μm, or about 1 μm to about 15 μm. The oxide-based positive active material may be, for example, single crystal particles or polycrystalline particles.

[0184] Sulfide-based positive electrode active materials may include, for example, Li-containing 2 S complex. Contains Li 2 The complexes of S may include, for example, Li 2 Complex of S and carbon, Li 2 S, composite of carbon and solid electrolyte, Li 2 Composites of S and solid electrolytes, Li 2 Complex of S and lithium salt, Li 2 S, lithium salt and carbon complex, Li 2 Composites of S and metal carbides, Li 2 S, composites of carbon and metal carbides, Li 2 Complexes of S and metal nitrides, Li 2 S, a composite of carbon and a metal nitride, or a combination thereof.

[0185] Li 2 The composite of S and carbon may include carbon. Carbon may be, for example, a material containing carbon atoms, and may be any material used as a conductive material in the art. Carbon may be, for example, crystalline carbon, amorphous carbon, or a combination thereof. Carbon may be, for example, a calcined product of a carbon precursor. Carbon may be, for example, a carbon nanostructure. The carbon nanostructure may be, for example, a one-dimensional carbon nanostructure, a two-dimensional carbon nanostructure, a three-dimensional carbon nanostructure, or a combination thereof. The carbon nanostructure may include, for example, carbon nanotubes, carbon nanofibers, carbon nanobelts, carbon nanorods, graphene, graphene oxide (GO), reduced graphene oxide (rGO), graphene balls (GB), or a combination thereof. Carbon may be, for example, porous carbon or nonporous carbon. Porous carbon may include, for example, periodic and ordered two-dimensional or three-dimensional pores. Porous carbon may include, for example, carbon black (such as Ketjen black, acetylene black, conductive acetylene black, thermal black, and channel black), graphite, activated carbon, or a combination thereof. The form of carbon may be, for example, a particle form, a sheet form, a fibrous form, etc., but is not limited thereto, and any carbon used in the art may be adapted here. Li 2The preparation method of the composite of S and carbon can be a dry method, a wet method or a combination thereof, but is not limited thereto. 2 The manufacturing method of the composite of S and carbon may be, for example, grinding, heat treatment, deposition, etc., but is not limited thereto, and may be any method used in the art.

[0186] Li 2 The composite of S, carbon and a solid electrolyte may include carbon and a solid electrolyte. 2 The description provided by the composite of S and carbon is to understand carbon. The solid electrolyte may be, for example, an amorphous solid electrolyte that can be used as an ion conductive material in the art. The solid electrolyte may be, for example, an inorganic solid electrolyte. The solid electrolyte may be, for example, a crystalline solid electrolyte, an amorphous solid electrolyte, or a combination thereof. The solid electrolyte may be, for example, a sulfide solid electrolyte, an oxide solid electrolyte, or a combination thereof. The sulfide solid electrolyte includes, for example, Li, S, and P, and may optionally further include a halogen element. The sulfide solid electrolyte may be selected from the sulfide solid electrolytes used in the solid electrolyte layer. For example, the sulfide solid electrolyte may have a carbon content of about 1×10 -5 S / cm or more ionic conductivity. The sulfide-based solid electrolyte may include, for example, a selected 3 PO 4 -Li 2 SO 4 , Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiX (wherein X can be a halogen element), Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n may be positive numbers, and Z may be one of Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (wherein p and q may be positive numbers, and M may be one of P, Si, Ge, B, Al, Ga, and In), Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2) and Li 7- x PS 6-x I x (where 0≤x≤2). The oxide-based solid electrolyte may include, for example, Li, O, and transition metal elements, and may optionally include other elements. For example, the oxide-based solid electrolyte may have a relative humidity of about 1×10 -5 The solid electrolyte has an ionic conductivity of S / cm or more. The oxide solid electrolyte can be selected from the oxide solid electrolytes used in the solid electrolyte layer. The solid electrolyte can be, for example, a mixture of a sulfide solid electrolyte and a lithium salt. For example, the solid electrolyte can be Li 3 PO 4 -Li 2 SO 4 A mixture of a binary lithium salt or Li 3 PO 4 -Li 2 SO 4 A mixture with a ternary lithium salt.

[0187] Li 2 The composite of S and a solid electrolyte may include a solid electrolyte.2 A composite of S, carbon and solid electrolyte is provided to understand the solid electrolyte.

[0188] Li 2 The complex of S and lithium salt may include a lithium salt compound. The lithium salt compound does not include, for example, sulfur (S) atoms. The lithium salt compound may be, for example, a binary compound comprising lithium and an element of a type (or species) selected from Groups XIII to XVII of the periodic table (e.g., consisting of lithium and an element of a type (or species) selected from Groups XIII to XVII of the periodic table). The binary compound may include, for example, a compound selected from LiF, LiCl, LiBr, LiI, LiH, Li 2 S. Li 2 O. Li 2 Se, Li 2 Te、Li 3 N.Li 3 P.Li 3 As、Li 3 Sb、LiI 3 and LiB 3 The lithium salt compound may be, for example, a ternary compound consisting of lithium and two types (kinds) of elements selected from Groups XIII to XVII of the periodic table. The ternary compound may include, for example, a ternary compound selected from Li 3 OCl、LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiAlO 2 、LiAlCl 4 、LiNO 3 , Li 2 CO 3 , LiBH 4 , Li 3 BO 3 , Li 3 PO 4 , Li 4 NCl、Li 5 NCl 2 and Li 3 BN 2 The lithium salt compound may be one or more lithium halide compounds selected from LiF, LiCl, LiBr and LiI. 2 The composite of S and a solid electrolyte may include a solid electrolyte. 2The description of the solid electrolyte used in the composite of S, carbon and solid electrolyte is provided to understand the solid electrolyte. 2 The composite of S and solid electrolyte may include, for example, Li 2 S and selected from LiF, LiCl, LiBr, LiI, LiH, Li 2 S. Li 2 O. Li 2 Se, Li 2 Te、Li 3 N.Li 3 P.Li 3 As、Li 3 Sb、LiI 3 and LiB 3 A complex of one or more lithium salts thereof.

[0189] Li 2 The composite of S, lithium salt and carbon may include a lithium salt compound and carbon. 2 The complex of S and carbon provides a description to understand carbon.

[0190] Li 2 The composite of S and metal carbide may include metal carbide. The metal carbide may be, for example, a two-dimensional metal carbide. The two-dimensional metal carbide may be, for example, MXene. The two-dimensional metal carbide may be, for example, MXene. n+1 C n T x (M is a transition metal, T is a terminal group, T is O, OH and / or F, n=1, 2 or 3, and x represents the number of terminal groups). The two-dimensional metal carbide can be, for example, Ti 2 CT x ,、(Ti 0.5 ,Nb 0.5 ) 2 CT x , Nb 2 CT x 、V 2 CT x 、Ti 3 C 2 T x ,(V 0.5 ,Cr 0.5 ) 3 C 2 T x 、Ti 3 CNT x 、 4 C 3 T x , Nb 4 C 3 Tx or a combination thereof. The surface of the two-dimensional metal carbide may be terminated with O, OH and / or F, and the total number of O, OH and / or F at the surface is the number of terminal groups.

[0191] Li 2 The composite of S, carbon and metal carbide may include carbon and metal carbide. 2 Carbon can be understood by referring to the description provided in conjunction with the aforementioned Li 2 The composites of S and metal carbides provide a description to understand metal carbides.

[0192] Li 2 The composite of S and metal nitride may include metal nitride. The metal nitride may be, for example, a two-dimensional metal nitride. The two-dimensional metal nitride may be, for example, M n+1 N n T x (M is a transition metal, T is a terminal group, T is O, OH and / or F, n=1, 2 or 3, and x represents the number of terminal groups.) The surface of the two-dimensional metal nitride can be terminated with O, OH and / or F, and the total number of O, OH and / or F at the surface is the number of terminal groups.

[0193] Li 2 The composite of S, carbon and metal nitride may include carbon and metal nitride. 2 Carbon can be understood by referring to the description provided in conjunction with the above Li 2 The complexes of S and metal nitrides provide a description to understand metal nitrides.

[0194] Li 2 The composite of S may further include, for example, a second fibrous sulfide-based solid electrolyte. 2 The complex of S can be the above Li 2 S and a second fibrous sulfide-based solid electrolyte composite or Li 2 S, a second fibrous sulfide-based solid electrolyte, a composite of the above carbon, a solid electrolyte, a lithium salt, a metal carbide or a metal nitride. The positive electrode layer may further include, for example, a first fibrous sulfide-based solid electrolyte.

[0195] By containing Li 2The composite of S further includes a second fibrous sulfide solid electrolyte, which can further inhibit or reduce the degradation of the lithium battery, and can further improve the cycle characteristics of the lithium battery. The size of the second fibrous sulfide solid electrolyte can be smaller than the size of the first fibrous sulfide solid electrolyte. The length and / or thickness of the second fibrous sulfide solid electrolyte can be about 50% or less, about 40% or less, about 30% or less, about 20% or less, or about 10% or less of the length and / or thickness of the first fibrous sulfide solid electrolyte, respectively. The length and / or thickness of the second fibrous sulfide solid electrolyte can be about 0.1% to about 50%, about 0.5% to about 40%, about 1% to about 30%, about 1% to about 20%, or about 1% to about 10% of the length and / or thickness of the first fibrous sulfide solid electrolyte, respectively. For example, the second fibrous sulfide solid electrolyte can have the same shape as the first fibrous sulfide solid electrolyte, and have a size smaller than the size of the first fibrous sulfide solid electrolyte. In some embodiments, the second fibrous sulfide-based solid electrolyte may have a reduced length and / or thickness, in which case the second fibrous sulfide-based solid electrolyte may be easily distributed in the Li-containing 2 If (for example, when) the second fibrous sulfide-based solid electrolyte has such a reduced length and / or thickness, degradation of the lithium battery can be further suppressed or reduced, and the cycle characteristics of the lithium battery can be further improved.

[0196] The size of the sulfide-based positive active material may be, for example, about 0.1 μm to about 50 μm, about 0.5 μm to about 30 μm, about 0.5 μm to about 20 μm, or about 1 μm to about 10 μm. 2 The size of S may be, for example, about 1 nm to about 10 μm, about 10 nm to about 5 μm, about 10 nm to about 3 μm, or about 10 nm to about 1 μm. 2 The size of the complex of S may be, for example, about 0.1 μm to about 50 μm, about 0.5 μm to about 30 μm, about 0.5 μm to about 20 μm, or about 1 μm to about 10 μm.

[0197] The shape of the positive electrode active material can be, for example, a particle shape, such as a spherical shape, an elliptical shape, etc. The particle size of the positive electrode active material is not limited, and is within the applicable range of the positive electrode active material of the all-solid-state secondary battery of the prior art. The content (e.g., amount) of the positive electrode active material in the positive electrode layer 10 is not limited, and is within the applicable range of the positive electrode layer of the all-solid-state secondary battery of the prior art. The content (e.g., amount) of the positive electrode active material included in the positive electrode active material layer 12 can be, for example, about 10wt% to about 99wt%, about 10wt% to about 90wt%, about 10wt% to about 80wt%, about 10wt% to about 70wt%, or about 10wt% to about 50wt%.

[0198] Cathode layer: solid electrolyte

[0199] The positive electrode active material layer 12 may also include, for example, a solid electrolyte. The solid electrolyte may be, for example, a sulfide-based solid electrolyte. The solid electrolyte included in the positive electrode layer 10 may be the same as or different from the solid electrolyte included in the solid electrolyte layer 30. The solid electrolyte may be understood by referring to the description provided in conjunction with the solid electrolyte layer 30.

[0200] The solid electrolyte included in the positive electrode active material layer 12 may have a D50 (average particle size) smaller than the D50 (average particle size) of the solid electrolyte included in the solid electrolyte layer 30. For example, the D50 (average particle size) of the solid electrolyte included in the positive electrode active material layer 12 may be about 90% or less, about 80% or less, about 70% or less, about 60% or less, about 50% or less, about 40% or less, about 30% or less, or about 20% or less of the D50 (average particle size) of the solid electrolyte included in the solid electrolyte layer 30. The D50 (average particle size) may be, for example, a median particle size (D50). The D50 corresponds to a particle size corresponding to about 50% cumulative volume when a particle size distribution measured by, for example, laser diffraction is calculated starting from a smaller particle size.

[0201] The content (e.g., amount) of the solid electrolyte included in the positive active material layer 12 may be, for example, about 1 wt% to about 40 wt%, about 1 wt% to about 30 wt%, about 1 wt% to about 20 wt%, or about 1 wt% to about 10 wt% of the total weight of the positive active material layer 12.

[0202] Positive electrode layer: conductive material

[0203] The positive electrode active material layer 12 may also include a conductive material. The conductive material may be, for example, a carbon-based conductive material, a metal-based conductive material, or a combination thereof. The carbon-based conductive material may be, for example, graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or a combination thereof, but is not limited thereto, and may be any carbon-based conductive material used in the art. The metal-based conductive material may be a metal powder, a metal fiber, or a combination thereof, but is not limited thereto, and may be any material used as a metal-based conductive material in the art. The content (e.g., amount) of the conductive material included in the positive electrode active material layer 12 may be, for example, about 1wt% to about 30wt%, about 1wt% to about 20wt%, or about 1wt% to about 10wt% of the total weight of the positive electrode active material layer 12.

[0204] Positive electrode layer: Binder

[0205] The positive electrode active material layer 12 may further include a binder. The binder may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited thereto, and may be any material used as a binder in the art. The content (e.g., amount) of the binder included in the positive electrode active material layer 12 may be, for example, about 1 wt% to about 10 wt% of the total weight of the positive electrode active material layer 12. No binder may be provided.

[0206] Positive electrode layer: other additives

[0207] The positive electrode active material layer 12 may further include additives such as a filler, a coating agent, a dispersant, and an ion conductive aid in addition to the aforementioned positive electrode active material, solid electrolyte, binder, and conductive material.

[0208] Here, one or more of the above-mentioned fillers, coating agents, dispersants, ion conductive aids, etc. that may be included in the positive electrode active material layer 12 may also be any one or more suitable materials generally used in electrodes of all-solid-state secondary batteries.

[0209] Positive electrode layer: positive electrode current collector

[0210] The positive electrode collector 11 may be, for example, a plate or foil including indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof (e.g., composed of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof). The positive electrode collector 11 may not be provided. The thickness of the positive electrode collector 11 may be, for example, about 1 μm to about 100 μm, about 1 μm to about 50 μm, about 5 μm to about 25 μm, or about 10 μm to about 20 μm.

[0211] The positive electrode current collector 11 may include, for example, a base film and a metal layer disposed on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. In some embodiments, the base film may be an insulator. If (e.g., when) the base film includes an insulating thermoplastic polymer, if (e.g., when) a short circuit occurs, the base film softens or liquefies and blocks the battery operation, thereby suppressing the rapid increase of the current. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), or alloys or conjugates thereof. The metal layer may be used as an electrochemical fuse and is cut off in the event of an overcurrent to perform a short circuit prevention function. The limiting current and the maximum current can be adjusted by adjusting the thickness of the metal layer. The metal layer can be plated or deposited on the substrate film. When the thickness of the metal layer is reduced, the limiting current and / or the maximum current of the positive electrode collector 11 are reduced, causing the stability of the lithium battery in the case of a short circuit to increase. For external connection, a lead tab can be added to the metal layer. The lead tab can be welded to the metal layer or the metal layer / substrate film laminate by ultrasonic welding, laser welding, spot welding, etc. During welding, the substrate film and / or the metal layer can be melted, and the metal layer can be electrically connected to the lead tab. In order to make the welding between the metal layer and the lead tab stronger, a metal sheet can be added between the metal layer and the lead tab. The metal sheet can be a sheet of the same material as the metal of the metal layer. The metal sheet can be, for example, a metal foil or a metal mesh. The metal sheet can be, for example, an aluminum foil, a copper foil, or a stainless steel (SUS) foil. By placing the metal sheet on the metal layer and welding it to the lead tab, the lead tab can be welded to the metal sheet / metal layer laminate or the metal sheet / metal layer / substrate film laminate. During welding, the metal layer or metal layer / metal sheet laminate can be electrically connected to the lead tab while the base film, metal layer and / or metal sheet melt. The metal sheet and / or lead tab can be added to a portion of the metal layer. The thickness of the base film can be, for example, about 1 μm to about 50 μm, about 1.5 μm to about 50 μm, about 1.5 μm to about 40 μm, or about 1 μm to about 30 μm. If (for example, when) the base film has a thickness of these ranges, the weight of the electrode assembly can be more effectively reduced. The melting point of the base film can be, for example, about 100°C to about 300°C, about 100°C to about 250°C, or about 100°C to about 200°C. If (for example, when) the base film has a melting point of these ranges, the base film can be melted and easily bonded to the lead tab in the process of welding the lead tab.In order to improve the adhesion between the base film and the metal layer, a surface treatment such as a corona treatment can be performed on the base film. The thickness of the metal layer can be, for example, about 0.01 μm to about 3 μm, about 0.1 μm to about 3 μm, about 0.1 μm to about 2 μm, or about 0.1 μm to about 1 μm. If (for example, when) the metal layer has a thickness of these ranges, the stability of the electrode assembly can be ensured while maintaining conductivity. The thickness of the metal sheet can be, for example, about 2 μm to about 10 μm, about 2 μm to about 7 μm, or about 4 μm to about 6 μm. If (for example, when) the metal sheet has a thickness of these ranges, the connection between the metal layer and the lead tab can be more easily performed. The positive current collector 11 with such a structure can help reduce the weight of the positive electrode layer, and ultimately help increase the energy density of the positive electrode layer and the all-solid-state secondary battery.

[0212] Positive electrode layer: the first inert component

[0213] Reference Figures 4 to 5 and Figures 8 to 12 The all-solid-state secondary battery 1 may further include a first inert member 40 , 40 a , 40 b disposed on at least one side (eg, one side or both sides (eg, opposite sides)) of the negative electrode collector 21 and the other side of the positive electrode collector 11 .

[0214] The first inert members 40 , 40 a , 40 b may be understood by referring to the description provided in conjunction with the first inert members 40 , 40 a , 40 b of the negative electrode layer.

[0215] Positive electrode layer: the second inert component

[0216] Reference Figures 6 to 12 The positive electrode layer 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the positive electrode current collector 11. The second inert member 50 may be disposed on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the positive electrode layer 10.

[0217] Reference Figure 7 , Fig. 9 and Fig.11 , the second inert member 50 may be disposed on at least one side (e.g., one side or both sides (e.g., opposite sides)) of the positive active material layer 12, and disposed between the solid electrolyte layer 30 and the positive current collector 11 opposite to the solid electrolyte layer 30. The second inert member 50 may not be disposed on one side surface of the positive current collector 11. Figure 6 , Figure 8 , Fig.10 and Fig.12, the second inert member 50 may be disposed on at least one side surface (e.g., one side surface or two side surfaces (e.g., opposite side surfaces)) of each of the positive electrode active material layer 12 and the positive electrode current collector 11. By including the second inert member 50, during the manufacture and / or charging and discharging of the all-solid-state secondary battery 1, the rupture of the solid electrolyte layer 30 may be prevented or reduced, and the all-solid-state secondary battery 1 may be improved. In an all-solid-state secondary battery 1 that does not include the second inert member 50, during the manufacture and / or charging and discharging of the all-solid-state secondary battery 1, an uneven pressure may be applied to the solid electrolyte layer 30 in contact with the positive electrode layer 10, and thus cracks may be generated in the solid electrolyte layer 30, and the growth of the cracks by the lithium metal may increase the possibility of a short circuit.

[0218] Reference Figures 6 to 12 , regarding the all-solid secondary battery 1 , the thickness of the second inert member 50 may be greater than the thickness of the first negative electrode active material layer 22 . For example, the thickness of the second inert member 50 may be greater than the thickness of the solid electrolyte layer 30 .

[0219] Reference Figures 6 to 12 , the second inert member 50 may surround the side of the positive electrode layer 10 and may be in contact with the solid electrolyte layer 30. In some embodiments, the second inert member 50 surrounds the side surface of the positive electrode layer 10 and contacts the solid electrolyte layer 30, and in this case, cracks in the portion of the solid electrolyte layer 30 that is not in contact with the positive electrode layer 10 that may be caused by the pressure difference during pressing can be effectively suppressed or reduced. The second inert member 50 may surround the side surface of the positive electrode layer 10 and may be separated from the negative electrode layer 20 (e.g., the first negative electrode active material layer 22). The second inert member 50 may surround the side surface of the positive electrode layer 10 and contact the solid electrolyte layer 30, and may be separated from the negative electrode layer 20. In this regard, the possibility of a short circuit due to physical contact between the positive electrode layer 10 and the first negative electrode active material layer 22 or overcharge of lithium is suppressed or reduced. In some embodiments, the second inert member 50 is simultaneously (e.g., synchronously) disposed on the side surfaces of the positive active material layer 12 and the positive current collector 11, in which case the possibility of a short circuit due to contact between the positive current collector 11 and the negative electrode layer 20 can be more effectively suppressed or reduced.

[0220] Reference Figures 6 to 12, the second inert member 50 extends from one side surface of the positive electrode layer 10 to the end of the solid electrolyte layer 30. By extending the second inert member 50 to the end of the solid electrolyte layer 30, cracks generated at the end of the solid electrolyte layer 30 can be suppressed or reduced. The end of the solid electrolyte layer 30 refers to the outermost portion in contact with the side surface of the solid electrolyte layer 30. The second inert member 50 may extend to the outermost portion in contact with the side surface of the solid electrolyte layer 30. The second inert member 50 may be separated from the negative electrode layer 20 (e.g., the first negative electrode active material layer 22). The second inert member 50 may extend to the end of the solid electrolyte layer 30, but not in contact with the negative electrode layer 20. In some embodiments, the second inert member 50 may fill the space extending from one side surface of the positive electrode layer 10 to the end of the solid electrolyte layer 30.

[0221] The area of ​​the positive electrode active material layer 12 or the positive electrode layer 10 (for example, the cross-sectional area of ​​the positive electrode active material layer 12 or the cross-sectional area of ​​the positive electrode layer 10 relative to the stacking direction or thickness direction of the all-solid-state secondary battery 1) may be smaller than the area of ​​the first negative electrode active material layer 22 or the negative electrode layer 20 (for example, the cross-sectional area of ​​the first negative electrode active material layer 22 or the cross-sectional area of ​​the negative electrode layer 20 relative to the stacking direction or thickness direction of the all-solid-state secondary battery 1). The area of ​​the positive electrode active material layer 12 or the positive electrode layer 10 (for example, the cross-sectional area of ​​the positive electrode active material layer 12 or the cross-sectional area of ​​the positive electrode layer 10 relative to the stacking direction or thickness direction of the all-solid-state secondary battery 1) may be smaller than the area of ​​the solid electrolyte layer 30 (for example, the cross-sectional area of ​​the solid electrolyte layer 30 relative to the stacking direction or thickness direction of the all-solid-state secondary battery 1).

[0222] The second inert member 50 may be, for example, a gasket. In some embodiments, a gasket is used as the second inert member 50, and in this case, cracking of the solid electrolyte layer 30 due to a pressure difference in a pressing process may be effectively suppressed or reduced.

[0223] The second inert member 50 may have, for example, a single-layer structure. In some embodiments, the second inert member 50 may have a multi-layer structure. The multi-layer structure may have, for example, a two-layer structure, a three-layer structure, or a four-layer structure, and by having a multi-layer structure, the physical properties of the second inert member 50 may be more accurately controlled or selected.

[0224] In some embodiments, part or all of the second inert member 50 may be arranged to be spaced apart from the side surface of the positive electrode active material layer 12. By arranging part or all of the second inert member 50 to be spaced apart from the side surface of the positive electrode active material layer 12, the manufacturing process of the all-solid-state secondary battery 1 becomes easier, and the manufacturing speed of the all-solid-state secondary battery 1 can be increased. By arranging part or all of the second inert member 50 to be spaced apart from the side surface of the positive electrode active material layer 12, the volume change in the side direction of the positive electrode active material layer 12 during charging and discharging is more effectively allowed, thereby further improving the life characteristics of the all-solid-state secondary battery 1. The distance between the second inert member 50 and the side surface of the positive electrode active material layer 12 may be, for example, about 0.1 μm to about 10 mm, about 1 μm to about 1 mm, about 1 μm to about 500 μm, about 1 μm to about 100 μm, about 1 μm to about 50 μm, or about 1 μm to about 10 μm.

[0225] Reference Figures 1 to 12 In some embodiments, the second inert member 50 may be selected from the materials used in the first inert members 40, 40a, 40b described previously. The second inert member 50 may not include (e.g., may exclude) electrode active materials, for example. The second inert member 50 may be, for example, a flame retardant inert member, an electronically insulating inert member, an ionically insulating inert member, or an elastic inert member.

[0226] Solid electrolyte layer

[0227] Solid electrolyte layer: solid electrolyte

[0228] Reference Figures 1 to 12 , the all-solid-state secondary battery 1 may include a solid electrolyte layer 30 disposed between the negative electrode layer 20 and the positive electrode layer 10. The solid electrolyte layer 30 may include, for example, a solid electrolyte or a combination of a solid electrolyte and a gel electrolyte.

[0229] The solid electrolyte may include, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof.

[0230] The solid electrolyte may be, for example, a sulfide-based solid electrolyte. The sulfide-based solid electrolyte may include, for example, a material selected from Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiX (wherein X can be a halogen element), Li 2 SP 2 S 5 -Li 2 O. Li 2 SP2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n may be positive numbers, and Z may be one of Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (wherein p and q may be positive numbers, and M may be at least one of P, Si, Ge, B, Al, Ga, and In), Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6- x Br x (where 0≤x≤2) and Li 7-x PS 6-x I x (where 0≤x≤2) is at least one of the following. Sulfide solid electrolytes are prepared by melting, quenching or mechanical grinding of a solid such as Li 2 S and P 2 S 5In some embodiments, the solid electrolyte may be amorphous, crystalline, or a mixture thereof. In some embodiments, the solid electrolyte may include, for example, sulfur (S), phosphorus (P), and lithium (Li) as constituent elements at least selected from the aforementioned sulfide-based solid electrolyte materials. For example, the solid electrolyte may be a Li 2 SP 2 S 5 In some embodiments, the material comprising Li 2 SP 2 S 5 The material can be used as a sulfide-based solid electrolyte constituting the solid electrolyte. In this case, Li 2 S and P 2 S 5 The mixing molar ratio can be (for example Li 2 S:P 2 S 5 =) from about 20:80 to about 90:10, from about 25:75 to about 90:10, from about 30:70 to about 70:30 and from about 40:60 to about 60:40.

[0231] The sulfide-based solid electrolyte may include, for example, an argyrodite-type or (kind of) solid electrolyte (eg, an argyrodite solid electrolyte) represented by Formula 1:

[0232] Formula 1

[0233] Li + 12-n-x A n+ X 2- 6-x Y - x

[0234] Wherein, A may be P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta, X may be S, Se or Te, and Y may be Cl, Br, I, F, CN, OCN, SCN or N 3 , 1≤n≤5, and 0≤x≤2. The sulfide-based solid electrolyte may be, for example, a sulfide-based solid electrolyte selected from Li 7-x PS 6-x Cl x (0≤x≤2), Li 7-x PS 6-x Br x (0≤x≤2) and Li 7-x PS 6-x I x(where x satisfies the condition of 0≤x≤2) and one or more argyrodite-type or (kind) compounds (e.g., argyrodite compounds). The sulfide-based solid electrolyte may be, for example, a sulfide-based solid electrolyte selected from Li 6 PS 5 Cl, Li 6 PS 5 Br and Li 6 PS 5 I. Compounds of one or more argyrodite types or (species) (e.g., argyrodite compounds).

[0235] The argyrodite type or (kind) of solid electrolyte (e.g., argyrodite solid electrolyte) may have a density of about 1.5 g / cc to about 2.0 g / cc. In some embodiments, the argyrodite type or (kind) of solid electrolyte (e.g., argyrodite solid electrolyte) may have a density of about 1.5 g / cc or greater, in which case the internal resistance of the all-solid-state secondary battery may be reduced, and the penetration of Li into the solid electrolyte layer may be effectively suppressed or reduced.

[0236] The oxide-based solid electrolyte can be, for example, Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2,0≤y<3)、BaTiO 3 、Pb(Zr,Ti)O 3 (PZT), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT)(0≤x<1, 0≤y<1), PB(Mg 3 Nb 2 / 3 ) 3 -PbTiO 3 (PMN-PT), HfO 2 、SrTiO 3 SnO 2 、CeO 2 、Na 2 O, MgO, NiO, CaO, BaO, ZnO, ZrO 2 , Y 2 O 3 、Al 2 O 3 、TiO 2 、SiO 2 , Li 3 PO 4, Li x Ti y (PO 4 ) 3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO 4 ) 3 (0 < x < 2, 0 < y < 1, 0 < z < 3), Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 (0 ≤ x ≤ 1, 0 ≤ y ≤ 1), Li x La y TiO 3 (0 < x < 2, 0 < y < 3), Li 2 O, LiOH, Li 2 CO 3 , LiAlO 2 , Li 2 O - Al 2 O 3 - SiO 2 - P 2 O 5 - TiO 2 - GeO 2 , Li 3+x La 3 M 2 O 12 (M = Te, Nb or Zr, 0 ≤ x ≤ 10) or combinations thereof. The oxide - type solid electrolyte is manufactured, for example, by a sintering method.

[0237] The oxide - type solid electrolyte can be, for example, selected from Li 7 La 3 Zr 2 O 12 (LLZO) and Li 3+x La 3 Zr 2-a M a O 12 (M - doped LLZO, M = Ga, W, Nb, Ta or Al, 0 < a < 2, 0 ≤ x ≤ 10) among the garnet - type (or species) solid electrolytes (e.g., garnet solid electrolytes).

[0238] In some embodiments, the polymer solid electrolyte may include a mixture of a lithium salt and a polymer (or a polymer having an ion conductive functional group). The polymer solid electrolyte may be, for example, a polymer electrolyte that is in a solid state at about 25° C. and about 1 atm. For example, the polymer solid electrolyte may not include a liquid. The polymer solid electrolyte may include a polymer, and the polymer may be, for example, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene (PVDF-HFP), poly(styrene-b-ethylene oxide) block or reduced copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block or reduced copolymer, poly(styrene-ethylene oxide-styrene) block or reduced copolymer, polystyrene sulfonate (PSS), polyvinyl fluoride (PVF), poly(methyl methacrylate) (PMMA), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polyethylenedioxythiophene (PEDOT), polypyrrole (PPY), polyaniline, polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, sulfonated poly(ether ketone) (SPEEK), sulfonated poly(arylene ether ketone sulfone) (SPAEKKS), sulfonated poly(arylene ether ketone) (SPAEK), poly[bis(benzimidazolobenzoisoquinolinone)] (SPBIBI), lithium 9,10-diphenylanthracene-2-sulfonate (DPASLi + ) or a combination thereof, but not limited thereto, and any material used as a polymer electrolyte in the art can be used herein. Any lithium salt that can be used as a lithium salt in the art can be used herein. The lithium salt can be, for example, LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiCF 3 SO 3 、Li(CF 3 SO 2 ) 2 N, LiC 4 F 9 SO 3 、LiAlO 2 、LiAlCl 4 、LiN(C x F 2x+1 SO 2 )(C y F 2y+ 1 SO 2) (wherein, x and y are both 1 to 20), LiCl, LiI or a mixture thereof. The polymer included in the polymer solid electrolyte can be, for example, a compound comprising about 10 or more, about 20 or more, about 50 or more, or about 100 or more repeating units. The weight average molecular weight of the polymer included in the polymer solid electrolyte can be, for example, about 1000 Daltons or more, about 10,000 Daltons or more, about 100,000 Daltons or more, or about 1,000,000 Daltons or more.

[0239] The gel electrolyte may be, for example, a polymer gel electrolyte. In some embodiments, the gel electrolyte may be in a gel state without containing a polymer.

[0240] In some embodiments, the polymer gel electrolyte may include a liquid electrolyte and a polymer, or may include an organic solvent and a polymer having an ion conductive functional group. The polymer gel electrolyte may be, for example, a polymer electrolyte that is in a gel state at about 25° C. and about 1 atm. In some embodiments, the polymer gel electrolyte may have a gel state in a state where there is no liquid therein. The liquid electrolyte used in the polymer gel electrolyte may be, for example: a mixture including an ionic liquid and a lithium salt; a mixture including a lithium salt and an organic solvent; a mixture including an ionic liquid and an organic solvent; or a mixture including a lithium salt, an ionic liquid and an organic solvent. The polymer used in the polymer gel electrolyte may be selected from the polymer used in the solid polymer electrolyte. The organic solvent may be selected from the organic solvent used for the liquid electrolyte. The organic solvent can be, for example, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether or a mixture thereof. The lithium salt can be selected from the lithium salt used in the polymer solid electrolyte. Ionic liquid refers to a salt or room temperature molten salt that is liquid at room temperature and is composed only of ions and has a melting point of room temperature or lower. In some embodiments, the ionic liquid may be at least one selected from the group consisting of compounds comprising: a) at least one cation selected from ammonium, pyrrolidinium, pyridinium, pyrimidinium, imidazolium, piperidinium, pyrazolium, oxazolium, pyridazinium, phosphonium, sulfonium, triazolium, and mixtures thereof; and b) at least one cation selected from BF 4 - PF 6 - , AsF 6- , SbF 6 - 、AlCl 4 - , HSO 4 - , ClO 4 - , CH 3 SO 3 - CF 3 CO 2 - , Cl - Br - ,I - , BF 4 - 、SO 4 - CF 3 SO 3 - 、(FSO 2 ) 2 N - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 )(CF 3 SO 2 )N - and (CF 3 SO 2 ) 2 N - In some embodiments, the polymer solid electrolyte can be impregnated with a liquid electrolyte in a secondary battery to form a polymer gel electrolyte. The polymer gel electrolyte may also include inorganic particles. The polymer included in the polymer gel electrolyte may be, for example, a compound containing about 10 or more, about 20 or more, about 50 or more, or about 100 or more repeating units. The weight-average molecular weight of the polymer included in the polymer gel electrolyte may be, for example, about 500 Daltons or more, about 1000 Daltons or more, about 10,000 Daltons or more, about 100,000 Daltons or more, or about 1,000,000 Daltons or more.

[0241] Solid electrolyte layer: Binder

[0242] The solid electrolyte layer 30 may include, for example, a binder. The binder included in the solid electrolyte layer 30 may be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited to these. The binder may be any material that can be used as a binder in the art. The binder of the solid electrolyte layer 30 may be the same as or different from the binder included in each of the positive electrode active material layer 12 and the first negative electrode active material layer 22. No binder may be provided.

[0243] Based on the total weight of solid electrolyte layer 30, the content (e.g., amount) of the binder included in solid electrolyte layer 30 may be about 0.1 wt% to about 10 wt%, about 0.1 wt% to about 5 wt%, about 0.1 wt% to about 3 wt%, about 0.1 wt% to about 1 wt%, about 0 wt% to about 0.5 wt%, or about 0 wt% to about 0.1 wt%.

[0244] In this specification, substituents are derived by exchanging one or more hydrogen atoms with other atoms or functional groups in an unsubstituted parent group. Unless otherwise specified, the case where a functional group is considered to be "substituted" refers to the case where the functional group is substituted by one or more substituents selected from C1-C40 alkyl, C2-C40 alkenyl, C2-C40 alkynyl, C3-C40 cycloalkyl, C3-C40 cycloalkenyl and C7-C40 aryl. The case where a functional group is "optionally substituted" refers to the case where the functional group can be substituted by the above-mentioned substituents.

[0245] As used herein, a and b in the expression "Ca to Cb" refer to the number of carbon atoms of a particular functional group. For example, a functional group may include from a to b carbon atoms. For example, "C1-C4 alkyl" refers to an alkyl group having 1 to 4 carbon atoms, such as CH 3 -、CH 3 CH 2 -、CH 3 CH 2 CH 2 -、(CH 3 ) 2 CH-、CH 3 CH 2 CH 2 CH 2 -、CH 3 CH 2 CH(CH 3 )- and (CH 3 ) 3 C-.

[0246] Depending on the context, the nomenclature for a particular radical may include either a monoradical or a diradical. For example, if (e.g., when) a substituent requires two sites of attachment to the rest of the molecule, the substituent is understood to be a diradical. For example, a substituent designated by an alkyl group that requires two sites of attachment includes a diradical, such as -CH 2 -、-CH 2 CH 2 -、-CH 2 CH(CH 3 )CH 2 - etc. Other radical nomenclatures such as "alkylene" explicitly indicate that the radical is a diradical.

[0247] The term "alkyl" or "alkylene" used herein refers to a branched or unbranched aliphatic hydrocarbon group. In certain embodiments, the alkyl group may be substituted or unsubstituted. The alkyl group includes methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, cyclopropyl, cyclopentyl, cyclohexyl, cycloheptyl, etc., but need not be limited thereto, and each of them may be optionally substituted or unsubstituted. In certain embodiments, the alkyl group may have 1 to 6 carbon atoms. For example, C1-C6 alkyl may be methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, pentyl, 3-pentyl, hexyl, etc., but need not be limited thereto.

[0248] The term "alkenyl" used herein refers to a hydrocarbon group containing at least one carbon-carbon double bond and containing 2 to 20 carbon atoms, and alkenyl includes vinyl, 1-propenyl, 2-propenyl, 2-methyl-1-propenyl, 1-butenyl, 2-butenyl, cyclopropenyl, cyclopentenyl, cyclohexenyl, cycloheptenyl etc., without being limited thereto. In certain embodiments, alkenyl can be substituted or unsubstituted. In certain embodiments, alkenyl can have 2 to 40 carbon atoms.

[0249] The term "alkynyl" is a hydrocarbon group containing at least one carbon-carbon triple bond and containing 2 to 20 carbon atoms. Alkynyl includes ethynyl, 1-propynyl, 1-butynyl, 2-butynyl, etc., without limitation. In some embodiments, alkynyl can be substituted or unsubstituted. In some embodiments, alkynyl can have 2 to 40 carbon atoms.

[0250] As used herein, the term "cycloalkyl" refers to a fully saturated carbocyclic ring or a fully saturated ring system. For example, the term refers to cyclopropyl, cyclobutyl, cyclopentyl or cyclohexyl.

[0251] The term "aromatic" as used herein refers to a ring or ring system having a conjugated π electron system, and includes carbocyclic aromatic groups (e.g., phenyl) and heterocyclic aromatic groups (e.g., pyridyl). The term includes monocyclic or fused polycyclic rings (i.e., rings that share adjacent pairs of atoms), provided that the entire ring system is aromatic.

[0252] The term "aryl" as used herein refers to an aromatic ring whose ring backbone contains only carbon, a ring system (i.e., two or more fused rings sharing two adjacent carbon atoms), or a ring system in which multiple aromatic rings are connected by a single bond, -O-, -S-, -C(=O)-, -S(=O)-, or 2 -, -Si(Ra)(Rb)- (Ra and Rb can be independently C1-C10 alkyl), C1-C10 alkylene which is unsubstituted or substituted with halogen, or -C(=O)-NH- are connected to each other. If (for example, when) aryl is a ring system, each ring in the system is aromatic. For example, aryl includes but is not limited to phenyl, biphenyl, naphthyl, phenanthrenyl, tetraphenyl, etc. Aryl can be substituted or unsubstituted.

[0253] The term "heteroaryl" as used herein refers to an aromatic ring system having one ring, multiple fused rings, or multiple rings connected by single bonds, -O-, -S-, -C(=O)-, -S(=O)-, 2 -, -Si(Ra)(Rb)- (Ra and Rb are independently alkyl groups having 1 to 10 carbon atoms), C1-C10 alkylene groups which are unsubstituted or substituted with halogen, or -C(=O)-NH- rings connected to each other, wherein at least one ring atom is not carbon (i.e., at least one ring atom is a heteroatom). In a fused ring system, one or more heteroatoms may be present in only one ring. In a fused ring system, one or more heteroatoms may be present in multiple rings. For example, heteroatoms include, but are not necessarily limited to, oxygen, sulfur, and nitrogen. For example, heteroaryl groups may include, but are not limited to, furanyl, thienyl, imidazolyl, quinazolinyl, quinolyl, isoquinolyl, quinoxalinyl, pyridyl, pyrrolyl, oxazolyl, indolyl, etc., but are not limited thereto.

[0254] The term "halogen" as used herein is a stable element belonging to Group XVII of the Periodic Table of Elements, and may be, for example, fluorine, chlorine, bromine or iodine (or, for example, fluorine and / or chlorine).

[0255] Unless otherwise mentioned in this specification, the weight average molecular weight of a polymer is measured by gel permeation chromatography (GPC) relative to polystyrene standards.

[0256] The present disclosure will be explained in more detail through the following examples and comparative examples. However, these examples are intended to illustrate the present disclosure, and the scope of the inventive concept is not limited thereto.

[0257] Preparation of sulfide composite positive electrode active materials

[0258] Preparation Example 1: Li 2 S-LiI-CNF composite positive electrode active material

[0259] Li 2 S and LiI were mixed in a weight ratio of about 30:20. The mixture was mechanically ground using a ball mill to prepare Li 2 S-LiI composite. The grinding conditions were about 25°C, about 510 rpm, and about 10 hours.

[0260] Li 2 The S-LiI composite and carbon nanofibers (CNF) were mixed in a weight ratio of about 50:10. The mixture was mechanically ground using a ball mill to prepare Li 2 S-LiI-CNF composite. The grinding conditions are about 25°C, about 510 rpm and about 10 hours. Li 2 The S-LiI-CNF composite was used as the composite cathode active material.

[0261] Manufacturing of all-solid-state secondary batteries

[0262] Example 1: elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles: CNT: binder = 3:1:0.28)

[0263] Fabrication of the positive electrode layer

[0264] Preparation of Li 2 O-ZrO 2 (LZO)-coated LiNi 0.8 Co 0.15 Al 0.05 O 2 (NCM) as a positive electrode active material. The LZO-coated positive electrode active material was prepared according to the method disclosed in Korean Patent Publication No. 10-2016-0064942 (the entire contents of which are incorporated herein by reference). Li 2O ... 6 PS 5Cl (D50 = about 0.5 μm, crystalline) was prepared as a solid electrolyte. A polytetrafluoroethylene (PTFE) binder was prepared as a binder. Carbon nanofibers (CNF) were prepared as a conductive material. These materials were mixed with a xylene solvent in a weight ratio of positive electrode active material: solid electrolyte: conductive material: binder = about 84:11:3:2. The slurry was formed into a sheet and vacuum dried at about 40°C for about 8 hours to prepare a positive electrode sheet. The prepared positive electrode sheet was placed on a carbon layer of a positive electrode current collector consisting of an aluminum foil coated with a carbon layer on one side, and then hot rolled at a temperature of about 85°C. The total thickness of the positive electrode layer is about 112 μm. The thickness of the positive electrode active material layer is about 92 μm, and the thickness of the carbon-coated aluminum foil is about 20 μm.

[0265] The initial charge capacity of the positive electrode active material layer was measured using the half cell. The initial charge capacity of the positive electrode active material layer was about 25 mAh.

[0266] Fabrication of negative electrode layer

[0267] A SUS (stainless steel) foil having a thickness of about 10 μm is prepared as a negative electrode current collector. Silicon (Si) particles having a particle size of about 1 μm are prepared as negative electrode active materials. Carbon nanotubes are prepared as fibrous carbon materials. Carbon nanotubes include a carbon nanotube primary structure and a carbon nanotube secondary structure. The carbon nanotube primary structure consists of a carbon nanotube unit. The length of the carbon nanotube unit is about 200 nm to about 300 nm, and the diameter of the carbon nanotube unit is about 5 nm to about 10 nm. The carbon nanotube secondary structure is formed by aggregating a plurality of carbon nanotube units. The length of the carbon nanotube secondary structure is about 5 μm, and the diameter of the carbon nanotube secondary structure is about 40 nm.

[0268] About 4 g of a mixed powder of silicon (Si) particles and carbon nanotubes in a weight ratio of about 3:1 is placed in a container, and about 4 g of an NMP solution containing about 7 wt % of a lithium-substituted polyacrylic acid (Li-PAA) binder is added thereto to prepare a mixed solution. NMP is slowly added to the prepared mixed solution while stirring the mixed solution to prepare a slurry. The prepared slurry is coated on a SUS substrate using a rod coater, dried in air at about 80°C for about 10 minutes, and then vacuum dried at about 40°C for about 10 hours to prepare a laminate. The prepared laminate is cold-rolled to flatten its surface to prepare a negative electrode layer having a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer is about 27 μm. Li-PAA is prepared by mixing polyacrylic acid and LiOH at a ratio of about 1 mole of LiOH per about 1 mole of polyacrylic acid (-COOH group), and then drying.

[0269] The initial charge capacity of the first negative electrode active material layer was measured using the half cell described previously. The initial charge capacity of the first negative electrode active material layer was about 9.2 mAh.

[0270] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer is about 0.37. By charging from the first open circuit voltage to about 4.25 V (vs. Li / Li + ) to determine the initial charge capacity of the positive electrode active material layer. By charging from the second open circuit voltage to about 0.01 V (vs. Li / Li + ) to determine the initial charge capacity of the first negative electrode active material layer.

[0271] Regarding each of Examples 2 to 5 and Comparative Example 1, wherein the ratio (B / A) is about 0.24 to about 0.45, B is the initial charge capacity of the first negative active material layer, and A is the initial charge capacity of the positive active material layer.

[0272] Fabrication of solid electrolyte layer

[0273] Based on about 98.5 parts by weight of the solid electrolyte, about 1.5 parts by weight of an acrylic binder was added to the Li 6 PS 5 A mixture is prepared by adding a Cl solid electrolyte (D50 = about 3.0 mm, crystalline), wherein the solid electrolyte is a argyrodite type (or species) (e.g., argyrodite) crystal. Octyl acetate is added to the prepared mixture while stirring to prepare a slurry. The prepared slurry is coated on a non-woven fabric placed on a PET substrate using a rod coater and dried in air at about 80° C. for about 10 minutes to prepare a laminate. The prepared laminate is vacuum dried at about 80° C. for about 2 hours to prepare a solid electrolyte layer.

[0274] Inert component: elastic sheet

[0275] A porous polyurethane foam sheet having a thickness of about 50 μm was prepared as the elastic sheet.

[0276] Manufacturing of all-solid-state secondary batteries

[0277] The laminate is prepared by placing the negative electrode layer on the solid electrolyte layer so that the first negative electrode active material layer is in contact with the solid electrolyte layer, and placing the positive electrode layer on the solid electrolyte layer so that the positive electrode active material layer is in contact with the solid electrolyte layer.

[0278] The prepared laminate was flat-pressed at about 85° C. and a pressure of about 500 MPa for about 30 minutes. Through this pressurization treatment, the solid electrolyte layer was sintered and the battery characteristics were improved. The thickness of the solid electrolyte layer after sintering was about 30 μm. The Li ions as argyrodite type (or species) (e.g., argyrodite) crystals included in the solid electrolyte layer after sintering were 6 PS 5 The density of the Cl solid electrolyte is about 1.6 g / cc. The area of ​​the solid electrolyte layer is equal to the area of ​​the negative electrode layer. An elastic sheet is additionally placed on the positive electrode current collector of the pressed laminate.

[0279] The laminate further including the elastic sheet is placed in a bag and vacuum-sealed to manufacture an all-solid-state secondary battery. Portions of the positive electrode collector and the negative electrode collector extend to the outside of the sealed battery and serve as positive and negative electrode terminals.

[0280] Example 2: elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles: CNT: binder = 3.2:0.8:0.28)

[0281] An all-solid-state secondary battery was manufactured in substantially the same manner as in Example 1, except that the composition ratio of the negative electrode active material to the fibrous carbon-based material was changed to about 3.2:0.8 (4:1).

[0282] Example 3: elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles: CNT: binder = 3.5:0.5:0.28)

[0283] An all-solid-state secondary battery was manufactured in substantially the same manner as in Example 1, except that the composition ratio of the negative electrode active material to the fibrous carbon-based material was changed to about 3.5:0.5 (7:1).

[0284] Example 4: elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles: CNT: binder = 3.6:0.4:0.28)

[0285] An all-solid-state secondary battery was manufactured in substantially the same manner as in Example 1, except that the composition ratio of the negative electrode active material to the fibrous carbon-based material was changed to about 3.6:0.4 (9:1).

[0286] Example 5: elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles: CNT: binder = 2:2:0.28)

[0287] An all-solid-state secondary battery was manufactured in substantially the same manner as in Example 1, except that the composition ratio of the negative electrode active material to the fibrous carbon-based material was changed to about 2:2 (1:1).

[0288] Comparative Example 1: elastic sheet (50 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles: CNT: binder = 3.6:0.4:0)

[0289] An all-solid-state secondary battery was manufactured in substantially the same manner as in Example 4, except that no binder was used.

[0290] Reference Example 1: elastic sheet (100 μm) / positive electrode layer (112 μm, NCA) / solid electrolyte layer (30 μm) / negative electrode layer (17 μm, Ag-C+binder)

[0291] An all-solid-state secondary battery was manufactured in substantially the same manner as in Example 1, except that the negative electrode layer produced by the method described below was used and the thickness of the elastic sheet was changed to about 100 μm.

[0292] Fabrication of negative electrode layer

[0293] A SUS foil having a thickness of about 10 μm is prepared as a negative electrode current collector. About 4 g of a mixture containing carbon black (CB) and silver (Ag) in a weight ratio of about 3: 1 is placed in a container, and then about 4 g of an NMP solution containing about 7 wt % of a PVDF binder (#9300 from Kureha) is added to prepare a mixed solution. NMP is slowly added to the prepared mixed solution while stirring the mixed solution to prepare a slurry. The prepared slurry is coated on a SUS substrate using a rod coater, dried in air at about 80 ° C for about 10 minutes, and then vacuum dried at 40 ° C for 10 hours to prepare a laminate. The prepared laminate is cold-rolled to flatten its surface, thereby preparing a negative electrode layer having a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer is about 7 μm.

[0294] Example 6: Positive electrode layer (113.8 μm, Li 2 S-LiI-CNF) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles: CNT: binder = 3:1:0.28)

[0295] An all-solid-state secondary battery was manufactured in substantially the same manner as in Example 1, except that a positive electrode layer including a sulfide-based positive electrode active material was used and the elastic sheet was omitted.

[0296] Fabrication of the positive electrode layer

[0297] The Li prepared in Preparation Example 1 2 The S-LiI-CNF composite was prepared as a positive electrode active material. Lithium argyrodite type (or species) (e.g., argyrodite) crystals (D50 = about 3.0 μm, crystals) were prepared. 6 PS 5 Cl was prepared as a solid electrolyte. PTFE was prepared as a binder. A positive electrode mixture was prepared by mixing the composite positive electrode active material, the solid electrolyte, and the binder in a weight ratio of about 60:40:1.2. The positive electrode mixture was obtained by mixing using a ball mill.

[0298] The positive electrode mixture is placed on at least one side (e.g., one side or both sides (e.g., opposite sides)) of a positive electrode current collector consisting of an aluminum foil coated with carbon on one side, and a positive electrode layer is manufactured by flat pressing at a pressure of about 200 MPa for about 10 minutes. The total thickness of the positive electrode layer is about 113.8 μm. The thickness of the positive electrode active material layer is about 93.8 μm, and the thickness of the carbon-coated aluminum foil is about 20 μm.

[0299] In Example 6, the ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer is about 0.35. By charging from the first open circuit voltage to about 2.8 V (vs. Li / Li + ) to determine the initial charge capacity of the positive electrode active material layer. By charging from the second open circuit voltage to about 0.01 V (vs. Li / Li + ) to determine the initial charge capacity of the first negative electrode active material layer.

[0300] Comparative Example 2: Positive electrode layer (113.8 μm, Li 2 S-LiI-CNF) / solid electrolyte layer (30 μm) / negative electrode layer (37 μm, Si particles: CNT: binder = 3.6:0.4:0)

[0301] An all-solid-state secondary battery was manufactured in substantially the same manner as in Example 4, except that the positive electrode layer of Example 6 was used and the binder was omitted.

[0302] Reference Example 2: Elastic sheet (50 μm) / positive electrode layer (113.8 μm, Li 2 S-LiI-CNF) / solid electrolyte layer (30μm) / negative electrode layer (17μm, Ag-C+binder)

[0303] An all-solid-state secondary battery was manufactured in substantially the same manner as in Example 6, except that a negative electrode layer produced by the method described below was used, and an elastic sheet having a thickness of about 50 μm was used.

[0304] Fabrication of negative electrode layer

[0305] A SUS foil having a thickness of about 10 μm is prepared as a negative electrode current collector. About 4 g of a mixture of carbon black (CB) and silver (Ag) containing a weight ratio of about 3: 1 is placed in a container, and then about 4 g of an NMP solution containing about 7 wt % of a PVDF binder (#9300 from Kureha) is added to prepare a mixed solution. NMP is slowly added to the prepared mixed solution while stirring the mixed solution to prepare a slurry. The prepared slurry is coated on a SUS substrate using a rod coater, dried in air at about 80 ° C for about 10 minutes, and then vacuum dried at about 40 ° C for about 10 hours to prepare a laminate. The prepared laminate is cold-rolled to flatten its surface, thereby preparing a negative electrode layer having a first negative electrode active material layer / negative electrode current collector structure. The thickness of the first negative electrode active material layer is about 7 μm.

[0306] Evaluation Example 1-1: Evaluation of Volume Change during Charge and Discharge (NCA Positive Electrode Active Material)

[0307] For the all-solid-state secondary batteries prepared according to Example 1 and Reference Example 1, in the charging and discharging experiments of Evaluation Example 2, only the charging step (e.g., behavior or task) of the first cycle was performed, and then a scanning electron microscope image of the cross-section of each all-solid-state secondary battery was obtained and the change in thickness was confirmed.

[0308] After the first cycle of charging, a lithium metal layer is formed between the first negative electrode active material layer and the negative electrode collector.

[0309] Regarding the all-solid-state secondary battery of Example 1, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode collector after initial charge was about 8 μm (smaller than the thickness of the first negative electrode active material layer after charge (about 34 μm)).

[0310] The thickness increase of the all-solid-state secondary battery of Example 1 after the initial charge is about 10% or less of the initial thickness of the all-solid-state secondary battery. As a result, the volume change of the all-solid-state secondary battery of Example 1 during the charging and discharging process is suppressed or reduced.

[0311] In the all-solid secondary battery of Example 1, an elastic member having a thickness of about 50 μm was used to allow for volume changes during charge and discharge. The energy density of the all-solid secondary battery was slightly reduced due to the inclusion of the elastic member having a thickness of about 50 μm.

[0312] Regarding the all-solid-state secondary battery of Reference Example 1, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode collector after initial charge was about 30 μm (larger than the thickness of the first negative electrode active material layer after charge (about 7 μm)).

[0313] The thickness of the all-solid-state secondary battery of Reference Example 1 after the initial charge increased by more than about 15% of the initial thickness of the all-solid-state secondary battery. As a result, the all-solid-state secondary battery of Reference Example 1 changed significantly in volume during the charging and discharging process.

[0314] In the all-solid secondary battery of Reference Example 1, an elastic member having a thickness of about 100 μm was used to allow for volume changes during charge and discharge. As a result, the energy density of the all-solid secondary battery was further reduced by including the elastic member having a thickness of about 100 μm.

[0315] Evaluation Example 1-2: Evaluation of Volume Change during Charge and Discharge (Li 2 S-LiI-CNF positive electrode active material)

[0316] For the all-solid-state secondary batteries prepared according to Example 6 and Reference Example 2, in the charging and discharging experiments of Evaluation Example 2, only the charging step (e.g., behavior or task) of the first cycle was performed, and then a scanning electron microscope image of the cross-section of each all-solid-state secondary battery was obtained, and the change in thickness was confirmed.

[0317] After the first cycle of charging, a lithium metal layer is formed between the first negative electrode active material layer and the negative electrode current collector.

[0318] Regarding the all-solid secondary battery of Example 6, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode collector after initial charge was about 8 μm (smaller than the thickness of the first negative electrode active material layer after charge (34 μm)).

[0319] The thickness increase after the initial charge of the all-solid-state secondary battery of Example 6 was about 5% or less of the initial thickness of the all-solid-state secondary battery. As a result, the volume change of the all-solid-state secondary battery of Example 6 during the charging and discharging process was not significant.

[0320] In the all-solid secondary battery of Example 6, no elastic member is used to allow volume changes during charge and discharge. As a result, there is no reduction in energy density of the all-solid secondary battery caused by the elastic member.

[0321] Regarding the all-solid secondary battery of Reference Example 2, the thickness of the lithium metal layer formed between the first negative electrode active material layer and the negative electrode collector after initial charge was about 30 μm (larger than the thickness of the first negative electrode active material layer (about 7 μm)).

[0322] The thickness of the all-solid-state secondary battery of Reference Example 2 after the initial charge increased by more than about 10% of the initial thickness of the all-solid-state secondary battery. As a result, the all-solid-state secondary battery of Reference Example 2 changed significantly in volume during the charging and discharging process.

[0323] In the all-solid secondary battery of Reference Example 2, an elastic member having a thickness of about 50 μm was used to allow for an increase in volume change during charge and discharge. By including an elastic member having a thickness of about 50 μm, the energy density of the all-solid secondary battery was slightly reduced.

[0324] Evaluation Example 2: Charging and Discharging Test

[0325] The charge / discharge characteristics of the all-solid secondary batteries manufactured according to Examples 1 to 5, Comparative Example 1, and Reference Example 1 were evaluated by the following charge and discharge test. The charge / discharge test was performed by placing the all-solid secondary batteries in a constant temperature bath at about 45°C.

[0326] In the first cycle, at about 0.5 mA / cm 2 The battery was charged at a constant current of about 12.5 hours until the battery voltage was about 3.9 V to about 4.25 V. Subsequently, the battery was charged at a constant current of about 0.5 mA / cm 2 The battery was discharged at a constant current for about 12.5 hours until the battery voltage reached about 2.5V.

[0327] In some embodiments, the charge / discharge characteristics of the all-solid secondary batteries manufactured in Example 6, Comparative Example 2, and Reference Example 2 were evaluated by the following charge and discharge tests. The charge / discharge test was performed by placing the all-solid secondary battery in a constant temperature bath at about 45°C.

[0328] In the first cycle, the battery was charged at a constant current of about 0.1 C for about 12.5 hours until the battery voltage reached about 2.5 V to about 2.8 V. Subsequently, the battery was discharged at a constant current of about 0.1 C for about 12.5 hours until the battery voltage reached about 0.3 V.

[0329] The discharge capacity of the first cycle was taken as the standard capacity.

[0330] After the second cycle, charging and discharging were performed under the same conditions as those of the first cycle up to about 500 cycles.

[0331] The cycle number refers to the number of cycles required for the discharge capacity to decrease to about 80% of the standard capacity after the second cycle. As the cycle number increases, it is considered to have excellent or suitable life characteristics.

[0332] Table 1

[0333]

[0334] As shown in Table 1, the all-solid-state secondary batteries of Examples 1 to 5 exhibited excellent or suitable life characteristics by suppressing volume change during charge and discharge and suppressing an increase in internal resistance.

[0335] The all-solid-state secondary batteries of Examples 1 to 5 have improved lifespan characteristics compared to the all-solid-state secondary battery of Comparative Example 1 that does not include a binder.

[0336] Regarding the all-solid-state secondary battery of Comparative Example 1, it was determined that the life characteristics of the all-solid-state secondary battery were reduced due to the disconnection of the conductive path caused by the separation of the electrodes and / or the separation of the negative electrode active material and the fibrous carbon-based material.

[0337] The all-solid-state secondary battery of Example 6 exhibits excellent or suitable life characteristics by suppressing volume change during charge and discharge and suppressing an increase in internal resistance.

[0338] The all-solid-state secondary battery of Example 6 has improved lifespan characteristics compared to the all-solid-state secondary battery of Comparative Example 2 that does not include a binder.

[0339] Regarding the all-solid-state secondary battery of Comparative Example 2, it is determined that the life of the all-solid-state secondary battery is reduced due to an increase in the interface resistance between the first negative electrode active material layer and the solid electrolyte due to the separation of the electrodes during the charging and discharging process, or an increase in the interface resistance between the first negative electrode active material layer and the negative electrode collector due to the separation of the electrode active material layer.

[0340] Evaluation Example 5: High-rate characteristic evaluation

[0341] The high rate characteristics of the all-solid secondary batteries of Examples 1 to 5 and Comparative Example 1 were evaluated by the following charge / discharge test. The charge / discharge test was performed by placing the all-solid secondary batteries in a constant temperature bath at about 45°C.

[0342] The all-solid-state secondary batteries of Examples 1 to 5, Comparative Example 1, and Reference Example 1 were charged at a constant current of about 0.1C at about 45°C until the voltage reached about 3.9V (vs. Li), and cut off at about 0.05C while maintaining a voltage of about 3.9V in a constant voltage mode. Subsequently, they were discharged at a constant current of about 0.1C until the voltage reached about 2.5V (vs. Li) (formation cycle).

[0343] The all-solid-state secondary battery that has undergone formation cycles is charged at about 45°C at a constant current of about 0.2C until the voltage reaches about 3.9V (vs. Li), and then discharged at a constant current of about 0.2C until the voltage reaches about 2.5V (vs. Li) (first cycle).

[0344] The all-solid-state secondary battery after the first cycle was charged at about 45°C at a constant current of about 0.2C until the voltage reached about 3.9V (vs. Li). Subsequently, it was discharged at a constant current of about 0.33C until the voltage reached about 2.5V (vs. Li) (second cycle).

[0345] The all-solid-state secondary battery after the second cycle was charged at about 45°C at a constant current of about 0.2C until the voltage reached about 3.9V (vs. Li). Subsequently, it was discharged at a constant current of about 0.5C until the voltage reached about 2.5V (vs. Li) (third cycle).

[0346] The all-solid-state secondary battery after the third cycle was charged at about 45°C at a constant current of about 0.2C until the voltage reached about 3.9V (vs. Li). Subsequently, it was discharged at a constant current of about 1.0C until the voltage reached about 2.5V (vs. Li) (the fourth cycle).

[0347] In all charge / discharge cycles, a rest time of 10 minutes was provided after each charge / discharge cycle. Some of the results of the room temperature charge and discharge experiments are shown in Table 2. The high rate characteristics are defined by Eq.

[0348] The high rate characteristics of the all-solid secondary batteries of Example 6, Comparative Example 2, and Reference Example 2 were evaluated by the following charge / discharge test. The charge / discharge test was performed by placing the solid secondary battery in a constant temperature bath at about 45°C.

[0349] The all-solid-state secondary batteries of Example 6 and Comparative Example 2 were charged at a constant current of about 0.1C rate at about 45°C until the voltage reached about 2.5V (vs. Li), and cut off at about 0.05C rate while maintaining a voltage of about 2.5V in a constant voltage mode. Subsequently, they were discharged at a constant current of about 0.1C rate until the voltage reached about 0.3V (vs. Li) (formation cycle).

[0350] The all-solid-state secondary battery that has undergone the formation cycle is charged at about 45°C at a constant current of about 0.2C until the voltage reaches about 2.5V (vs. Li), and then discharged at a constant current of about 0.2C until the voltage reaches about 0.3V (vs. Li) (first cycle).

[0351] The all-solid-state secondary battery after the first cycle was charged at about 45°C at a constant current of about 0.2C until the voltage reached about 2.5V (vs. Li). Subsequently, it was discharged at a constant current of about 0.33C until the voltage reached about 0.3V (vs. Li) (second cycle).

[0352] The all-solid-state secondary battery after the second cycle was charged at about 45°C at a constant current of about 0.2C until the voltage reached about 2.5V (vs. Li). Subsequently, it was discharged at a constant current of about 0.5C until the voltage reached about 0.3V (vs. Li) (third cycle).

[0353] The all-solid-state secondary battery after the third cycle was charged at about 45°C at a constant current of about 0.2C until the voltage reached about 2.5V (vs. Li). Subsequently, it was discharged at a constant current of about 1.0C until the voltage reached about 0.3V (vs. Li) (the fourth cycle).

[0354] In all charge / discharge cycles, a rest time of 10 minutes was provided after each charge / discharge cycle. Some of the results of the room temperature charge and discharge experiments are shown in Table 2. The high rate characteristics are defined by Eq.

[0355] Equation 1

[0356] High rate characteristics [%] = [discharge capacity of the fourth cycle / discharge capacity of the formation cycle] × 100

[0357] Table 2

[0358]

[0359] As shown in Table 2, compared with the all-solid-state secondary battery of Comparative Example 1, the all-solid-state secondary batteries of Examples 1 to 5 have improved high-rate characteristics.

[0360] Regarding the all-solid-state secondary batteries of Examples 1 to 5, although the first negative electrode active material layer undergoes a volume change during charge and discharge, since the binder is included in the first negative electrode active material layer, the conductive path between the negative electrode active material and the fibrous carbon-based material is maintained, and the uniformity of the electrode reaction is improved. Therefore, compared with the all-solid-state secondary battery of Comparative Example 1, the high-rate characteristics of the all-solid-state secondary batteries of Examples 1 to 5 are improved.

[0361] Compared with the all-solid-state secondary battery of Comparative Example 2, the all-solid-state secondary battery of Example 6 has improved high-rate characteristics.

[0362] Regarding the all-solid-state secondary battery of Example 6, although the volume of the first negative electrode active material layer changes during charging and discharging, since the binder is included in the first negative electrode active material layer, the conductive path between the negative electrode active material and the fibrous carbon-based material is maintained, and the uniformity of the electrode reaction is improved. As a result, the high-rate characteristics of the all-solid-state secondary battery of Example 6 are improved compared to the all-solid-state secondary battery of Comparative Example 2.

[0363] According to one aspect, since a fibrous carbon-based material and a binder are included in a negative electrode active material layer having an initial charge capacity smaller than that of a positive electrode active material layer, an all-solid secondary battery with reduced volume change during charge and discharge and improved cycle characteristics can be provided.

[0364] In the present disclosure, "not including a "component" or any "component", "excluding a "component" or any "component", "not containing a "component"", etc. means that the "component" is not added, selected or used as a component in the composition or compound, but due to other impurities and / or external factors, the "component" may still be included in an appropriate amount.

[0365] The battery management system (BMS) device according to the embodiment of the present invention described herein and / or any other related device or component may be implemented using any suitable hardware, firmware (e.g., an application specific integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on separate IC chips. In addition, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device may be processes or threads that execute computer program instructions and interact with other system components to perform the various functions described herein, running on one or more processors in one or more computing devices. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device (such as a random access memory (RAM) as an example). The computer program instructions may also be stored in other non-temporary computer-readable media (such as a CD-ROM, a flash drive, etc. as an example). In addition, it should be appreciated by those skilled in the art that, without departing from the scope of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a particular computing device may be distributed to one or more other computing devices.

[0366] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for the purpose of limitation. The description of features or aspects within each embodiment should generally be considered to be applicable to other similar features or aspects in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, it will be understood by those of ordinary skill in the art that one or more suitable changes in form and details may be made therein without departing from the spirit and scope of the present disclosure as defined by the appended claims and their equivalents.

Claims

1. An all-solid-state secondary battery, comprising: positive electrode layer; Negative electrode layer; as well as a solid electrolyte layer between the positive electrode layer and the negative electrode layer, in, The positive electrode layer includes a positive electrode current collector and a positive electrode active material layer on one side of the positive electrode current collector. The negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer on one side of the negative electrode current collector. The first negative electrode active material layer comprises: Negative electrode active material, capable of forming an alloy or compound with lithium; Fibrous carbon-based materials; and Adhesives, The ratio of the initial charge capacity of the first negative electrode active material layer to the initial charge capacity of the positive electrode active material layer is 0.01 to 0.75, The initial charge capacity of the positive electrode active material layer is charged from the first open circuit voltage to the maximum charge voltage vs. Li / Li + to determine, and The initial charge capacity of the first negative electrode active material layer is charged from the second open circuit voltage to 0.01 V vs. Li / Li + to be sure.

2. The all-solid-state secondary battery according to claim 1, wherein: The negative electrode active material includes particles having a size of 2 μm or less, and The negative electrode active material has an aspect ratio of 5 or less.

3. The all-solid-state secondary battery according to claim 1, wherein: The negative electrode active material includes a metal negative electrode active material, and The metal negative electrode active material includes silicon, gold, platinum, palladium, silver, aluminum, bismuth, tin, zinc or a combination thereof.

4. The all-solid-state secondary battery according to claim 1, wherein: The first negative electrode active material layer includes a mixture of first particles and second particles, wherein the first particles include the negative electrode active material, and the second particles include the fibrous carbon-based material, and The second particles may be included in an amount of 10 wt % to 70 wt % based on 100 wt % of the total weight of the mixture.

5. The all-solid-state secondary battery according to claim 1, wherein: The size of the negative electrode active material is smaller than the length of the fibrous carbon material, and The ratio of the size of the negative electrode active material to the length of the fibrous carbon-based material is 1:10 to 1:2000.

6. The all-solid-state secondary battery according to claim 1, wherein: The fibrous carbon material is a conductive elastic material, The aspect ratio of the fibrous carbon-based material is 10 or more, and The fibrous carbon-based material includes an amorphous fibrous carbon-based material, a crystalline fibrous carbon-based material, or a combination thereof.

7. The all-solid-state secondary battery according to claim 1, wherein: The fibrous carbon-based material includes a fibrous carbon nanostructure, and The fibrous carbon nanostructure includes carbon nanotubes, carbon nanofibers, carbon nanobelts or a combination thereof.

8. The all-solid-state secondary battery according to claim 7, wherein: The carbon nanotubes include a carbon nanotube primary structure, a carbon nanotube secondary structure formed by agglomeration of a plurality of carbon nanotube primary structures, or a combination thereof, and The carbon nanotube primary structure is a single carbon nanotube unit.

9. The all-solid-state secondary battery according to claim 8, wherein: The carbon nanotube primary structure includes single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes or a combination thereof, and The diameter of the carbon nanotube primary structure is 1 nm to 20 nm, and the length of the carbon nanotube primary structure is 100 nm to 2 μm.

10. The all-solid-state secondary battery according to claim 8, wherein: The carbon nanotube secondary structure includes bundle-type carbon nanotubes, rope-type carbon nanotubes or a combination thereof, and The diameter of the carbon nanotube secondary structure is 2 nm to 50 nm, and the length of the carbon nanotube secondary structure is 500 nm to 1000 μm.

11. The all-solid-state secondary battery according to claim 1, wherein: The binder is a polymer binder, and the binder includes polar functional groups, The polar functional groups include carboxyl, hydroxyl, amide, aldehyde or a combination thereof. The polar functional groups are partially or completely substituted by lithium, and The binder includes lithium-substituted polyacrylic acid.

12. The all-solid-state secondary battery according to claim 1, wherein: The binder may be included in an amount of 0.1 to 20 parts by weight based on 100 parts by weight of the negative electrode active material.

13. The all-solid-state secondary battery according to claim 1, wherein: The thickness of the first negative electrode active material layer is 50% or less of the thickness of the positive electrode active material layer, and The first negative electrode active material layer has a thickness of 1 μm to 50 μm.

14. The all-solid-state secondary battery according to claim 1, further comprising a second negative electrode active material layer at least one of between the negative electrode current collector and the first negative electrode active material layer and between the first negative electrode active material layer and the solid electrolyte layer, The second negative electrode active material layer is a metal layer, and the metal layer includes lithium or a lithium alloy, and The second negative electrode active material layer has a thickness smaller than that of the first negative electrode active material layer.

15. The all-solid-state secondary battery according to claim 1, wherein: The positive electrode active material layer includes a positive electrode active material, The positive electrode active material includes a sulfide positive electrode active material, an oxide positive electrode active material or a combination thereof. The sulfide-based positive electrode active material includes nickel sulfide, copper sulfide, Li2S, a composite containing Li2S, or a combination thereof, and The oxide-based positive electrode active material includes lithium transition metal oxide, lithium-free metal oxide or a combination thereof, and the lithium transition metal oxide includes lithium cobalt oxide, lithium nickel oxide and lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium manganate, lithium iron phosphate or a combination thereof, wherein the lithium-free metal oxide includes iron oxide, vanadium oxide or a combination thereof.

16. The all-solid-state secondary battery according to claim 1, wherein: The positive electrode active material layer further comprises one or more selected from a solid electrolyte, a conductive material and a binder, The solid electrolyte includes a sulfide-based solid electrolyte, and The conductive material includes a carbon-based conductive material.

17. The all-solid-state secondary battery according to claim 1, wherein: The solid electrolyte layer includes a solid electrolyte or a combination of the solid electrolyte and a gel electrolyte, The solid electrolyte includes a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte or a combination thereof, and The gel electrolyte includes a polymer gel electrolyte.

18. The all-solid-state secondary battery according to claim 17, wherein: The sulfide solid electrolyte includes a sulfide-based solid electrolyte selected from the group consisting of Li2S-P2S5, Li2S-P2S5-LiX, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n , Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q , Li 7-x PS 6-x Cl x , Li 7-x PS 6-x Br x and Li 7-x PS 6-x I x At least one of: wherein, in Li2S-P2S5-LiX, X is a halogen, wherein, in Li2S-P2S5-Z m S n In which m and n are positive numbers, and Z is one of Ge, Zn and Ga, wherein in Li2S-SiS2-Li p MO q In which p and q are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In, wherein in Li 7-x PS 6-x Cl x , 0≤x≤2, where Li 7-x PS 6- x Br x , 0≤x≤2, where Li 7-x PS 6-x I x In the equation, 0≤x≤2, The sulfide solid electrolyte includes an argyrodite solid electrolyte. The argyrodite solid electrolyte comprises one or more selected from Li6PS5Cl, Li6PS5Br and Li6PS5I, and The argyrodite-based solid electrolyte has a density of 1.5 g / cc to 2.0 g / cc.

19. The all-solid-state secondary battery according to claim 1, wherein: At least one of the positive electrode current collector and the negative electrode current collector includes a base film and a metal layer on at least one side of the base film, The base film comprises a polymer, The polymer includes polyethylene terephthalate, polyethylene, polypropylene, polybutylene terephthalate, polyimide or a combination thereof, and The metal layer includes indium, copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium, lithium or alloys thereof.

20. The all-solid-state secondary battery according to claim 1, further comprising a first inert member on the other side of the positive electrode current collector and / or the other side of the negative electrode current collector, and The first inert member is an elastic member.

Citation Information

Patent Citations

  • Cathode for lithium ion secondary battery, and lithium ion secondary battery

    KR1020160064942A

  • Multi-beam particle beam system and method for operating same

    KR1020230135167A